Lutein reverses M2 macrophages polarization and exhibits antitumor effects on human triple-negative breast cancer cells - Redzyque Ramza Ramli; Siti Nur Hasyila Muhammad; Maryam Azlan; Asma Abdullah Nurul; Siti Norasikin Mohd Nafi; Agustine Nengsih Fauzi (Molecular Biology Reports, 2026)

Suppression of miR426 enhances photoprotection and chlorophyll stability via upregulation of ELIP2 in Arabidopsis thaliana - Arif Faisal Mustaffa; Syed Muhammad Iqbal Syed Othman; Nur Irdina Izzatie Mohd Zahid; M. Hafiz Che-Othman; Hoe-Han Goh; Muhammad Sajad; Ismanizan Ismail (Molecular Biology Reports, 2026)

The evolution of AI-integrated genome editing and its challenges - Matthew Tze Jian Wong; Nur Diyana Zulkifli; Thurgashini Ravichandran; Kalidasan Vasodavan; Osama Al-Shaibah; Galib Muhammad Shahriar Himel; Anusha Achuthan; Mohana Anita Anthonysamy; Kumitaa Theva Das (Mammalian Genome, 2026)

Evaluating soil CO₂ fluxes during the transition from peat swamp forest to an oil palm plantation - Nur Azima Busman; Akira Watanabe; Muhammad Zarul Shazreen; Faustina E. Sangok; Lulie Melling (Science of The Total Environment, 2026)

Elucidating the effect of reactor configuration on xylan recovery during reductive alkaline hydrogen peroxide pretreatment system with implications for scale-up - Nur Syahirah Ahmad Sobri; Shuhaida Harun; Wei Feng Ang; Peer Mohamed Abdul; Muhammad Zulhaziman Mat Salleh (Chemical Engineering Journal, 2026)

Optimization of ohmic-assisted thermochemical pretreatment of empty fruit bunch for enhanced hydrogen production and fermentation kinetics - Izzah Farhana Ab Aziz; Hasfalina Che Man; Muhammad Hazwan Hamzah; Rozita Omar; Nur Syakina Jamali; Ibrahim B. Dalha (Biomass and Bioenergy, 2026)

Joint inversion using cross-gradient as a mathematical modelling framework for subsurface imaging in landslide hazard assessment - Muhammad Fawzy Ismullah Massinai; Muhammad Taqiuddin Zakaria; Mohd Hariri Arifin; Nurul Asikin Mohd Araha; Nur Irdina Insyiraah Mohd Salwira (Acta Geophysica, 2026)

Field readiness of Raman-AI pipelines for microplastic analysis across environmental matrices - R. Muhammad Nur Nasyrah.; Nurul Muthmainnah Ramlan; Isnaeni Isnaeni; Dahlang Tahir (Journal of Hazardous Materials, 2026)

Geochemistry and sedimentology of cretaceous oceanic red beds (CORBs) of the Turonian Goru Formation (Sulaiman Range, Pakistan) - Ahmed Nur Dalmar; Shuja Ullah; Muhammad Hanif; Mahnoor Sabba; Abdalle Dahir Yusuf; Muhammad Rizwan (Journal of African Earth Sciences, 2026)

Genetic variation of grey pomfret Pampus cinereus along the Bangladesh and Malaysia coastlines with phylogeography in the Indo-West Pacific based on mitochondrial COI and Cyt β - M.M. Mahbub Alam; Md. Moshiur Rahman; Jayed Mahbub Aomio; Nur Asma Ariffin; Mohammad Asmat-Ullah; Shamima Nasren; Sarker Mohammed Ibrahim Khalil; Md. Abdullah-Al Mamun; Muhammad Anamul Kabir; Ahasan Habib (Ecological Genetics and Genomics, 2026)

Population genetics of climbing perch, Anabas testudineus (Bloch, 1792) in the waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Mutia Ramadhaniaty; Adrian Damora; Cut Tria Aswina; Putri Khairani Amalia Siregar; Nanda Ulfa Khaira; Muhammad Syukran; Puncak Joyontono; Muhammad Nasir; Nur Fadli; et al. (Ecological Genetics and Genomics, 2026)

Corrigendum to “A review on biohydrogen production through dark fermentation via the lactate pathway” [Bioresour. Technol. 454 (2026) 134726] - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Bio-VegeGrout for soil strength enhancement: Effects of fermentation period on mechanical performance and microstructural characteristics - Wan Aisyah Fadilah Wae AbdulKadir; Rohayu Che Omar; Simon Gregory; Farah 'Atiqah Abdul Azam; Megan Barnett; Muhammad Afiq Mohamed Akbar; Nur 'Atikah Mahazir (Bioresource Technology Reports, 2026)

Response surface optimization of polyethersulfone biocomposite membranes reinforced with pineapple crown leaf-derived microcrystalline cellulose for dye wastewater treatment - Utari Zulfiani; Fitriani Fitriani; Muh Nur Hidayat; Nurul Widiastuti; Muhammad Roil Bilad; Muqoyyanah (Bioresource Technology Reports, 2026)

Bimetallic ferro and lanthanum impregnated on nano HZSM-5 catalysts for the Reutealis trisperma oil hydroprocessing to rich aromatic jet fuel range - Muhammad Al Muttaqii; Abdul Aziz; Sugeng Priyanto; Indri Yati; Muh. Nur Khoiru Wihadi; Amalia Kurnia Amin; Kiky Corneliasari Sembiring; Hendris Hendarsyah Kurniawan; Sudibyo; Didik Prasetyoko; Reva Edra Nugraha; Lenny Marlinda; et al. (Bioresource Technology Reports, 2026)

Breeding practices and production systems of indigenous goats in two agro-ecological zones of North Maluku Province, Indonesia - Dwi Nur Happy Hariyono; Muhammad Ade Salim; Dyah Maharani; Eny Endrawati (Tropical Animal Health and Production, 2026)

Baseline Assessment of Coral Reef Condition, Diversity and Disease Prevalence in Darvel Bay, Northeastern Borneo - Aiman Azseri; Nur Angelie Agnezara Roger; Zepri Abdul Muhaimin; Mazni Muhammad Addin; Khairul Hisham Hariz; Siti Nur Hazwani Oslan; Khodzori Fikri Akmal (Thalassas: An International Journal of Marine Sciences, 2026)

Mapping Flood Co-Adaptation Strategies in a Vulnerable River Basin: Engaging Youth in Collaborative Decision-Making - Zulfaqar Sa’adi; Zainura Zainon Noor; Nur Syamimi Zaidi; Ee Ling Yong; Fateha Abdul Razak; Nurul Hana Mohamed; Zainab Mat Lazim; Ainul Syarmimi Rosli; Mohd Faiz Foze; Siti Hanna Elias; Khairunnisa Abdul Halim; Muhammad Burhanuddin Bahrodin; et al. (Environmental Management, 2026)

Correction: Drug induced TdP risks classification assay using electro-mechanical models of human ventricle based on CiPA framework - Aulia Khamas Heikhmakhtiar; Ali Ikhsanul Qauli; Yunendah Nur Fu’adah; Muhammad Adnan Pramudito; Iga Narendra Pramawijaya; Aroli Marcellinus; Kim Yoo Seok; Frederique Jos Vanheusden; Ki Moo Lim (Toxicological Research, 2026)

Establishment of callus culture, elicitation study, and NMR-based metabolomics of Artemisia vulgaris L. - Ali Muhammad Zakariya; Nur Kusaira Khairul Ikram; Dwi Kusuma Wahyuni; Mohd Zuwairi Saiman (In Vitro Cellular & Developmental Biology - Plant, 2026)
Artemisia vulgaris L. has attracted considerable interest for its pharmaceutical, agricultural, and cosmetic applications due to its rich bioactive metabolites. However, low metabolite yields and challenges in large-scale cultivation constrain its commercial potential. Therefore, this study aimed to optimize a callus regeneration system, develop a comprehensive metabolite profile of the callus culture, and assess the effects of elicitor treatments on metabolite biosynthesis pathways to identify optimal concentrations for enhanced metabolite production. In vitro callus cultures were initiated on Murashige and Skoog (MS) medium with varying levels of benzylaminopurine (BAP), α-naphthaleneacetic acid (NAA), and 2,4-dichlorophenoxyacetic acid (2,4-D) phytohormones. Callus cultures were evaluated for colour, texture, moisture content, and biomass, and metabolite profiling was conducted using nuclear magnetic resonance (NMR) platform. Elicitor treatments of the callus cultures with different concentrations of methyl jasmonate (MJ) and salicylic acid (SA) were analysed via NMR-based metabolomics. MS medium containing 2.0 mg L⁻ 1 BAP and 0.2 mg L⁻ 1 NAA was optimal for callus culture establishment and maintenance. A total of eighteen compounds were identified, including dihydroartemisinic acid, caffeic acid, and gallic acid. MJ and SA functioned as stress elicitors, modulating the tricarboxylic acid cycle, phenylpropanoid, and artemisinin biosynthesis pathways, although they had limited direct effects on artemisinin concentrations. Overall, this study optimized callus culture production, generated the first detailed metabolite profile, and highlighted the potential of elicitation strategies to enhance bioactive metabolite yields, providing a foundation for future metabolic engineering and industrial applications.

Retraction notice to “Effects of dumpsite leachate plumes on surface and groundwater and the possible public health risks” [Sci. Total Environ. 897 (2023) 165469] - Joseph Omeiza Alao; Abubakar Fahad; Hazem Ghassan Abdo; Daniel A. Ayejoto; Hussin Almohamad; Muhammad Sani Ahmad; Mohammed Shettima Nur; Theophilus Toro Danjuma; Mumeen Adebayo Yusuf; Olaleye Timilehin Francis; Alao Ovaioza Joy (Science of The Total Environment, 2026)

Stakeholder heterogeneity and governance implications in horseshoe crab exploitation: Evidence from coastal South Sumatra, Indonesia - Fauziyah; Darlian; Rozirwan; Fitri Agustriani; Muhammad Hendri; Amanda Astri Pratiwi Febrianti; Ellis Nurjuliasti Ningsih; Nur Rohmah; Nabila Aprianti; Fatimah; Yusli Wardiatno (Regional Studies in Marine Science, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

New horizons in treating emerging contaminants: From laboratory to real-world applications - Shakila Abdullah; Siti Amira Othman; Nur Aisyah Abdul Halim Lim; Farhad Ali; Muhammad Syafrudin (Current Opinion in Environmental Science & Health, 2026)

A review on biohydrogen production through dark fermentation via the lactate pathway - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Characterization and Wound-Healing Effects of Fucoidan from Sargassum polycystum Collected in South Sulawesi in a Staphylococcus aureus-Infected Rat Model - Fausyiah Sasmitha AB; Frederika Tangdilintin; Sulistiawati Sulistiawati; Siti Nur Fatimah; Stephanie Stephanie; Muhammad Nur Amir; Syamsiah Syamsiah; Ngoc Dan Thuy Nguyen; Taifo Mahmud; Muhammad Nasrum Massi; Marianti Manggau (Marine Biotechnology, 2026)

Synthesis, Physicochemical Characterization and Antibacterial Assessment of Curcumin/2-Hydroxypropyl-β-Cyclodextrin-Functionalized Silver Nanoparticles (cAgNPs) - Amirul Hakim Azmi; Nur Asyura Nor Amdan; Syed Mahmood; Riyanto Teguh Widodo; Muhammad Kumayl Abdulwahab; Zarif Mohamed Sofian (Journal of Pharmaceutical Innovation, 2026)

Circular Supply Chain Barriers Analysis with Multicriteria Decision Making Techniques: A Systematic Review and Bibliometric Analysis - Cucuk Nur Rosyidi; Danang Setiya Wijaya; Wakhid Ahmad Jauhari; Muhammad Hisjam; Lanndon Ocampo; Dana Marsetiya Utama (Circular Economy and Sustainability, 2026)

Impacts of infrastructure development on taxonomic and functional diversity of non-volant small mammals - Ummi Nur Syafiqah Daud; Muhammad Iqbal Md. Jamaluddin; Nor Adibah Ismail; Nurfatin Batrisyia Md. Ali; Noor Fatihah Najihah Arazmi; Norfazliyana Nordin; Saiful Hilmi Jamal Shuhaily; Fudzla Zulfa Khiruddin; Amirul Haikal Zainal; Shukor Md. Nor; Aisah Shukor; Mohammad Saiful Mansor (Biodiversity and Conservation, 2026)

Year-round fruiting by Muntingia calabura helps sustain urban frugivorous birds across tropical cityscapes - Muhammad Syafiq Yahya; Nuur Farhani Zulkifli; Sharifah Nur Atikah; Ahmad Razi Norhisham; Ruzana Sanusi; Badrul Azhar (Ornithology Research, 2026)

3D HepG2 spheroid model exhibits drug-specific response profiles validating their application in therapeutic screening - Wee Ling Choe; Ain Zubaidah Ayob; Muhammad Danish Ahmad Tarmizi; Nur’ain Salehen; Thamil Selvee Ramasamy (In Vitro Cellular & Developmental Biology - Animal, 2026)

The first record of the arboreal land snail Amphidromus leucoxanthus (Martens, 1864) from Peninsular Malaysia (Stylommatophora: Camaenidae) - Mohamad Afiq Aiman Asrin; Khairul Amar Zikrie Zainudin; Muhammad Amir Iqhwan Mohd Khaderi; Nur Muhammad Hazami Abdul Rahman; Faathrio Hudaya Zulfin; Mohammad Effendi Marzuki; Aainaa Amir; Kamarul Hambali (Molluscan Research, 2026)

Linking nitrogen transformations and soil δ15N to assess drivers of nitrogen losses across a tropical peat swamp forest and an oil palm plantation - Elizabeth Gachibu Wangari; Kien Yung Teo; Ricky Mwangada Mwanake; Faustina Elfrida Sangok; Herman Umbau Lindang; Auldry Chaddy; Sharon Yu Ling Lau; Fawad Khan; Nur Azima Busman; Kim San Lo; Hanna Vahter; Muhammad Kamil-Sardar; et al. (Journal of Environmental Management, 2026)

The evolution of stone flaking technology at Leang Panninge (South Sulawesi, Indonesia) from the Late Pleistocene to the ‘Toalean’ technocomplex - Suryatman; Akin Duli; David McGahan; Andi Muh. Saiful; Basran Burhan; Ratno Sardi; Zubair Mas’ud; Fardi Ali Syahdar; Muh. Alif; Muhammad Nur; Aisyah Arung Qalam; Iwan Sumantri; et al. (Archaeological and Anthropological Sciences, 2026)

A novel coffee-leaf bio-lure extracted using NADES for attracting Conopomorpha cramerella - Sylvia Sjam; Ade Rosmana; Gemini Alam; Vien Sartika Dewi; Shin-ichi Tebayashi; Muhammad Agung Wardiman; Nur Azizah Fitriyanti (International Journal of Tropical Insect Science, 2026)

LC-MS/MS-based dereplication and molecular networking of Ficus superba with identification and quantification of furanocoumarins - Muhammad Afiffikri Ahmad; Sarah Sofea Mohd Sali; Nur Hanis Syuhada Abdul Rauf; Nur Ain Sofia Mohd Khairi; Shamsul Khamis; Nurunajah Ab. Ghani; Juliana Yusoff; Nurulfazlina Edayah Rasol (Natural Product Research, 2026)

Chemometric analysis of microplastics in tropical beach sediments of Bali, Indonesia: Distribution, polymer composition, and coastal processes - Mohd Rashidi Abdull Manap; Nur Fariesya Athierah Mohd Fadil; Nur Hayatna Mukhni; Muhammad Ibadurrahman Imizan; Herculano Martinho; Julian Alape; Jannik Werner Dams; Bruno S. Marangoni; Giorgio S. Senesi; Ramizah Azis; Pande Gde Sasmita Julyantoro; Haruka Nakano (Regional Studies in Marine Science, 2026)

β-radiation exfoliation of LDH nanosheets for next-generation water treatment membranes - Muhammad ‘Adli Nor Azman; Pei Sean Goh; S. Selambakkannu; Yuyang Yao; Ahmad Fauzi Ismail; Khairulnadzmi Jamaluddin; Nur Diyana Suzaimi; Ahmad Syazwan Sahril (Journal of Environmental Chemical Engineering, 2026)

Indonesia's path to sustainable aviation fuel: Evaluating feedstock potential from agricultural residue - Afdal Adha; Muhammad Ilham Adhynugraha; Fithri Nur Purnamastuti; Fadli Cahya Megawanto; Budiyanto; Chairunnisa; Sherly Octavia Saraswati; Ilham Bagus Wiranto; Rinal Kharis; Indriasari; Fitrianto; Akhmad Amry; et al. (Biomass and Bioenergy, 2026)

Unlocking the biomedical potential of coffee pulp: Extraction methodologies and mechanistic insights of non-bean derivatives for health - Munasir; Syaiful Adam Maulana; Rizqi Aulia Nurlaili; Nuhaa Faaizatunnisa; Muhammad Naufal Ariesta; Gusti Nur Aida Fasha; Slamet Widiyanto (Bioresource Technology Reports, 2026)

Catboost regressor for monsoon rainfall forecasting in Malaysia using atmospheric Beryllium-7 concentration - Mohd Fauzi Haris; Norita Md Norwawi; Mohd Hafez Mohd Isa; Mohd Zaid Hassan Abdul Rahman; Nur Fatini Abdul Ghani; Muhammad Rawi Mohamed Zain (Modeling Earth Systems and Environment, 2026)

Environmetric-driven health risk assessment of indoor air quality and sick building syndrome in educational facilities through integrated pattern recognition and spatial epidemiology - Syazwan Aizat Ismail; Haslinda Mohamed Kamar; Nazri Kamsah; Nur Azzalia Kamaruzaman; Muhammad Iftishah Ramdan; Björn Crüts; Muaz Mohd Zaini Makhtar; Mohd Rafatullah; Aseem Vashisht (Air Quality, Atmosphere & Health, 2026)

NMR-based metabolomics of Indonesian jamu for diabetes: chemical composition, toxicity, and zebrafish behavioral impact - Muhammad Safwan Ahamad Bustamam; Wimbuh Tri Widodo; Mohd Zuwairi Saiman; Siti Munirah Mohd. Faudzi; Siok Geok Chong; Nur Diana Safura Mohd Ezmir; Emelia Asmara Md Daud; Sonny Kristianto; Intan Safinar Ismail (Natural Product Research, 2026)

Index based assessment of coastal vulnerability along the West Coast of Peninsular Malaysia: Evidence of climate change and anthropogenic impacts - Sreenivasulu Ganugapenta; Effi Helmy Ariffin; Wenjian Li; Siti Nur Hanani Zainuddin; Mohammad Ikhmal Siddiq Jefri Din; Masha Nur Salsabiela Menhat; Nurwani Mohd Zaki; Mardiha Mokhtar; Muhammad Rizal Razali; Khairul Nizam Abdul Maulud; Mohd Fuad Miskon (Ocean & Coastal Management, 2026)

A review of indoor air quality (IAQ) in classrooms: The effect of particulate matter (PM), gaseous pollutants, and airborne pathogens - Nurul Shahadah Roslan; Mohamad Nur Hidayat Mat; Muhammad Faiz Hilmi Rani (Environmental Pollution, 2026)

Stacking Ensemble Machine Learning for Cardiac Safety Assessment Using hiPSC-CM MEA Data - Muhammad Adnan Pramudito; Yunendah Nur Fuadah; Yoo Seok Kim; Ki Moo Lim (Annals of Biomedical Engineering, 2026)

Multi-epitope vaccine design against Nipah virus: An immunoinformatics approach targeting South and Southeast Asia populations - Moh. Royhan Afnani; Viol Dhea Kharisma; Aswin Rafif Khairullah; Abdugani Abdurasulov; Roza Abdyldayeva; Maksim Rebezov; Arli Aditya Parikesit; Vikash Jakhmola; Rollando Rollando; Arif Nur Muhammad Ansori (In Silico Pharmacology, 2026)

Machine learning enhanced ecoacoustic indices for coral reef species richness prediction in noise-impacted soundscapes - Muhammad Yafie Rachmat Rizky Hidayat; Jianfeng Tong; Nur Ainul Hidayat Kasim (Regional Studies in Marine Science, 2026)

Fibre glass in Asphalt: A Review of Current Trends in Durability and Performance - Muhammad Ainul Ariff Mohd Asri; Muhammad Naqiuddin Mohd Warid; Siti Nur Naqibah Kamarudin; Mohd Rosli Hainin (Next Research, 2026)

Biotechnological and nutraceutical evaluation of Boehmeria virgata root extract: Phytochemical profiling, antidiabetic bioactivity, and safety assessment - Haeria Doloking; Andi Andriani Musfar; Rahmi Fitri Lestari Jamal; Riska Yuniarti; Ainun Sakinah; Fitri Sea Febriani; Akmal Zulfi; Arif Setiawansyah; Muhammad Ikhlas Arsul; Alwiyah Nur Syarif; Muhammad Ikhwan Arsul (Biocatalysis and Agricultural Biotechnology, 2026)

GC-MS Profiling, Cytotoxicity and Antiviral Activity of Caulerpa lentillifera and C. macrodisca from Northern Coastal Waters of Borneo Island, Eastern Malaysia - Mohammad Tamrin Mohamad Lal; Elden Sai Long Chang; Zy Chee Wong; Leong Seng Lim; Muhammad Dawood Shah; Wahidatul Husna Zuldin; Gilbert Ringgit; Nur Azreen Arbi; Ahmad Hazim Abdul Aziz; Abdul Aziz Jaziri; Asep Awaludin Prihanto; Attabik Mukhamad Amrillah; et al. (Marine Biotechnology, 2026)

Agricultural Waste Valorisation in Gulf Countries: A Scoping Review Toward Circular Economy and Sustainable Policy Innovation - Nur Fathin Ruslan; Noormazlinah Ahmad; Mimi Sakinah Abdul Munaim; Mohd Zamri Che Wanik; Antonio Sanfilippo; Jayaprakash Saththasivam; Muhammad Qasim Ali (Circular Economy and Sustainability, 2026)

Whole-genome characterization and functional–structural analysis of GST variants in Orang Asli with comparative insights from Malays - Aishah Farliani Shirat; Muhammad Yusuf Abdul Zaid; Nurul Azmir Amir Hashim; Nurul Huda Mohamad Ikbal; Mohd Nur Fakhruzzaman Noorizhab; Eng Keng Seow; Mohammad Masrin Md Zahrin; Thane Moze Darumalinggam; Muhammad Danish Badrul Hisham; Teh Lay Kek; Mohd Zaki Salleh (In Silico Pharmacology, 2026)

Rolled amniotic membrane for practical vascular graft development: a scoping review - Ahmad Hafiz Murtadha; Nur Najmi Mohamad Anuar; Mohamad Fikeri Ishak; Muhammad Dain Yazid; Nadiah Sulaiman (Human Cell, 2026)

Improving In Silico Cardiac Safety Prediction by Consensus Averaging of Transmural Ventricular Cell Models - Nurul Qashri Mahardika T; Ali Ikhsanul Qauli; Yunendah Nur Fuadah; Aulia Khamas Heikhmakhtiar; Muhammad Adnan Pramudito; Ariyadi; Aroli Marcellinus; Yoo Seok Kim; Ki Moo Lim (Annals of Biomedical Engineering, 2026)

Morphometric and genetic variation of six soldierfish species (genus Myripristis, family: Holocentridae) harvested in Aceh Besar waters, Indonesia - Nadya Tirta; Essy Harnelly; Rania Feranita Fachri; Putri Khairani Amalia Siregar; Nanda Muhammad Razi; Nanda Ulfa Khaira; Mutia Ramadhaniaty; Sri Riska Rahayu; Nurlita Putri Anggraini; Raissha Amanda Siregar; Adrian Damora; Nur Fadli (Zoologischer Anzeiger, 2026)

Coastal morphological changes and response to Typhoon Rai events in Pahang’s coastline - Muhammad Zahir Ramli; Siti Nur Hanani Zainuddin; Mohd Shahrizal Ab Razak; Muhammad Mazmirul Abd Rahman; Siti Nurain Che Mohd Azmi; Muhammad Rizal Razali; Effi Helmy Ariffin (Regional Studies in Marine Science, 2026)

Application of integrated coagulation-flocculation and biofilter for the treatment of food-processing industrial wastewater: Performances, microbial community, and cost analysis - Setiyono; Heru Susanto; Sudarno; Muhammad Abdul Kholiq; Arifudin; Fajar Eko Priyanto; Ahmad Shoiful; Sandia Primeia; Hana Salsabila; Nur Muhamad Fuad; Yosep Widi Nugraha; Veny Luvita; et al. (Journal of Water Process Engineering, 2026)

Sulfur–regolith composite material for radiation shielding on Mars: A sustainable ISRU approach - Muhammad Nazrif Zamani; Norhazilan Md Noor; Sarehati Umar; Mohamad Shazwan Ahmad Shah; Muhammad Syahir Sarkawi; Asyraf Arif Abu Bakar; Nur Hafizah A. Khalid; Hanis Hazirah Arifin (Journal of Cleaner Production, 2026)

Recent advances in vaccination strategies against acute hepatopancreatic necrosis disease (AHPND) in shrimp for sustainable aquaculture industry: A comprehensive review - Tijani Isa; Riyanto Teguh Widodo; Suzita Mohd Noor; Nur Asyura Nor Amdan; Zulhisyam Abdul Kari; Norhidayah Mohd Taufek; Fathiah Mohamed Zuki; Alias Abdullah; Subha Bhassu; Zarif Mohamed Sofian; Sagir Mustapha; Didi Erwandi Mohamad Haron; et al. (Fish & Shellfish Immunology, 2026)

Drug induced TdP risks classification assay using electro-mechanical models of human ventricle based on CiPA framework - Aulia Khamas Heikhmakhtiar; Ali Ikhsanul Qauli; Yunendah Nur Fu’adah; Muhammad Adnan Pramudito; Iga Narendra Pramawijaya; Aroli Marcellinus; Kim Yoo Seok; Frederique Jos Vanheusden; Ki Moo Lim (Toxicological Research, 2026)

Impact of Drought on Agricultural Ecosystems, Biomass and Carbon Uptake in the Northern Part of Bangladesh Using Remote Sensing and Weather Station Data - Nur Hussain; Md Adnan Rahman; Muhammad Rezaul Rakib; Md. Nurul Islam; Md Kamruzzaman (Remote Sensing in Earth Systems Sciences, 2026)

Enhancing village-level spatial planning with unmanned aerial vehicles: A comparative study of direct georeferencing and ground control points - Gunawan Setyo Prabowo; Suprapedi Suprapedi; Muhammad Bisri; Wayan Firdaus Mahmudy; Ari Sugeng Budiyanta; Nur Sugi; Try Kusuma Wardana; Aries Asrianto Ramadian; Hartono Hartono; Rudi Choirul Anwar; Unggul Satrio Yudhotomo (Applied Geomatics, 2026)

The potential of natural deep eutectic solvent in polyphenol extraction of Timonius flavescens (Jacq) Baker as an anti-breast cancer agent and its toxicity evaluation - Muhammad Fauzan Lubis; Retno Murwanti; Poppy Anjelisa Zaitun Hasibuan; Sumaiyah Sumaiyah; Nur Aira Juwita; Ana Yulyana; Ririn Astyka; Sri Yuliasmi; Lokot Donna Lubis; Wardiyah Daulay; Khairani Fitri (Advances in Traditional Medicine, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Microplastics distribution on the beach sediment based on satellite remote sensing: A case study in Bali, Indonesia - Mohd Rashidi Abdull Manap; Muhammad Ibadurrahman bin Imizan; Jannik Werner Dams; Felipe D. Sepulveda; Anna Muratore; Lorenza Notargiacomo; Fulvio Ferrara; Nur Hayatna Mukhni (Journal of Contaminant Hydrology, 2026)

Automatic weed detection in paddy field: a review - Md. Monirul Islam; Siti Khairunniza-Bejo; Muhammad Saiful Ahmad Hamdani; Nur Azuan Husin (Journal of Plant Diseases and Protection, 2026)

Unveiling the bee pollinators interaction with Muntingia calabura: implications for urban biodiversity conservation in tropical cityscapes - Muhammad Syafiq Yahya; Nuur Farhani Zulkifli; Sharifah Nur Atikah; Ruzana Sanusi; Badrul Azhar; Ahmad Razi Norhisham (Journal of Insect Conservation, 2026)

The influence of community perceptions and practices on the sustainability of Pulau Kapas Marine Park - Muhammad Naqib Hasri; Nazli Aziz; Nurul Huda Sapehee; Nur Qamarina Mohmad Fuad; Ahmad Irsyad Ahmad; Tengku Balkis Tunku Shahar Tengku Abdul Rashid; Nurashiqin Sallih Udin; Abdul Rahman Abdul Latip (Journal of Coastal Conservation, 2026)

A framework for an effective nationwide seagrass data collection: a case study for Indonesia - Nurul Dhewani Mirah Sjafrie; Udhi Eko Hernawan; Pramaditya Wicaksono; Doddy M. Yuwono; Novi Susetyo Adi; Muhammad Hafizt; Muhammad Banda Selamat; Bayu Prayudha; Setiawan Djody Harahap; Huwaida Nur Salsabila; Jennifer Wijaya; Sofia Yuniar Sani; et al. (Ocean & Coastal Management, 2026)

Assessing the performance of random forest and deep forest algorithms for Mangrove canopy cover mapping using PlanetScope SuperDove imagery - Abhista Fawwaz Sahitya; Muhammad Kamal; Nur Mohammad Farda (Remote Sensing Applications: Society and Environment, 2026)

Prediction of average SDG scores by using support vector machine: a machine learning approach - Vikneswari Someetheram; Nur Ezlin Zamri; Muhammad Fadhil Marsani; Mohd Shareduwan Mohd Kasihmuddin; Mohd. Asyraf Mansor (Clean Technologies and Environmental Policy, 2026)

Impacts of logging disturbance on soil dynamics and fungal communities in Cherul Forest Reserve, Terengganu - Suzazsuzuludin Azrai; Mansor Patahayah; Samsuddin Ahmad Syazwan; Khairi Nur Sahira-Aimaa; Rasdianah Dahali; Muhammad Syahmi Hishamuddin (Applied Soil Ecology, 2026)

Modulation of Sirtuin-1 by Resveratrol as a Potential Therapy in Alleviating Metabolic Syndrome - Afiqq Aiman Abd Ghapor; Nurul Alimah Abdul Nasir; Muhammad Zulfiqah Sadikan; Norhafiza Razali; Nur Hidayah Reshidan (Cell Biochemistry and Biophysics, 2025)

Evaluation of the antiproliferative effect of Zingiber zerumbet essential oil against oral squamous cell carcinoma - Muhammad Amirul Amil; Kae Shin Sim; Nurul Jannah Mohd Asngari; Marina Mohd Bakri; Fathilah Abdul Razak; Lee Fah Yap; Syarifah Nur Syed Abdul Rahman (South African Journal of Botany, 2025)

Unveiling deep-sea fish communities through eDNA analysis during extreme upwelling events in Pantar Strait, Indonesia - Yulita Dwi Astuti; Nining Nursalim; Muhammad Danie Al Malik; Ekitia Reyza Syakal; Lilik Maslukah; Yusuf Jati Wijaya; Rizki Taqwa Putranto; Heru Nur Krisna; Ikhsan Mustaqim; Azza Fidyani Sintania Susanti; R. Dwi Susanto; Ni Kadek Dita Cahyani; et al. (Regional Studies in Marine Science, 2025)

Seismic velocity structure beneath the western Java region, Indonesia, from local earthquake tomography - Wandono Wandono; Mohamad Ramdhan; Atin Nur Aulia; Arya Bani Pangestu; Edi Hidayat; Syuhada Syuhada; Sri Widiyantoro; Nicholas Rawlinson; Titi Anggono; Bayu Pranata; Muhammad Maruf Mukti; Mufti Putra Maulana (Journal of Volcanology and Geothermal Research, 2025)

Microbiological, physicochemical, and sensory changes during masin--shrimp fermentation - An Bil'is Ekarosadi; Muhammad Nur Cahyanto; Dwi Larasatie Nur Fibri (International Journal of Gastronomy and Food Science, 2025)

Exceptionally low electrical hysteresis, soft, skin-mimicking gelatin-based conductive hydrogels for machine learning-assisted wireless wearable sensors - Anky Fitrian Wibowo; Nurwarrohman Andre Sasongko; Anita Puspitasari; Truong Tien Vo; Siti Aisyah Nurmaulia Entifar; Yulia Shara Sembiring; Jung Ha Kim; Muhamad Junda Azizi; Muhammad Nur Slamet; Junghwan Oh; Jae-Seong Park; Soyeon Kim; et al. (Chemical Engineering Journal, 2025)

Recovery of Coral Reefs: Changes in Hard Coral Cover at Pulau Bidong After a Tropical Storm - Mohmad Fuad Nur Qamarina; Marsya Maisarah Ahmad Zaimi; Siti Nurtahirah Jaafar; Muhammad Hafiz Borkhanuddin; Zainudin Bachok; Che Din Mohd Safuan (Thalassas: An International Journal of Marine Sciences, 2025)

Genetic Population of Rusty Jobfish Aphareus Rutilans (Cuvier, 1830), Including a New Sequence Record from South Aceh Waters Indonesia - Sri Riska Rahayu; Abdul Rahman Siregar; Mutia Ramadhaniaty; Nanda Muhammad Razi; Syamsul Rizal; Nur Fadli; Luvi Syafrida Handayani; Martin Wilkes; Mohd Nor Siti-Azizah; Su-fang Niu; Zainal Abidin Muchlisin (Thalassas: An International Journal of Marine Sciences, 2025)

Unveiling the Potential of Garcinia Atroviridis Root-Derived Phenolic Compounds Against Breast Cancer: Isolation, Network Pharmacology and In-Silico Approaches - Nur Salsabila Binti Ahmad Roslan; Miah Roney; Abdul Rashid Issahaku; Md. Nazim Uddin; Mohd Fadhlizil Fasihi Mohd Aluwi; Seema Zareen; Anke Wilhelm; Ahmad Mahfuz Gazali; Muhammad Nadeem Akhtar; Normaiza Binti Zamri (Journal of Pharmaceutical Innovation, 2025)

Harnessing Polysaccharides from Azadirachta Indica A. Juss. (neem) Leaves Using Microwave-Assisted Extraction for Anti-Hyperpigmentation Activity - Abu Hurairah Darwisy Alias; Muhammad Hasnun Md Yusoff; Nur Qistina Abdul Razak; Suhaila Sujani; Zahir Husain Kamari; Tin-Wui Wong; Idanawati Naharudin; Muhammad Ameerullah Sahudin; Mohammad Afiq Aizuddin Rosdi; Chee-Yuen Gan; Muhammad Hakimin Shafie (Journal of Pharmaceutical Innovation, 2025)

Climate mitigation through urban forests: ecosystem services and species diversity in Rimba Ilmu, Universiti Malaya, Malaysia - Nur Hanisah Rahim; Sarah Abdul Razak; Chng Saun Fong; Chang Xue; Khairunnisa Hasikin; Fatchur Rohman; Siti Nasuha Hamzah; Tabassum Yaseen; Alevcan Kaplan; Muhammad Nauman Khan; Sezai Ercisli (Genetic Resources and Crop Evolution, 2025)

Sustainable integration of aquaculture wastewater treatment using Chlorococcum sp. in photobioreactor systems: Evaluation of nutrient removal, biomass productivity, and operational performance - Zubair Hashmi; Ibrahim Maina Idriss; Rieza Zulrian Aldio; Nur Aqidah Donglah; Juliana Zaini; Yusuf Wibisono; Muhammad Roil Bilad (Algal Research, 2025)

Optimization and comparative modelling of RSM and ANN for the adsorptive removal of Remazol Brilliant Blue R dye using spent coffee ground biochar - Endar Hidayat; Nur Ain Hannani Hamid; Nur Maisarah Mohamad Sarbani; Sadaki Samitsu; Mitsuru Aoyagi; Hiroyuki Harada; Muhammad Aslam Mohd Safari (Chemosphere, 2025)

DNA barcoding of fish from Singkil peat swamp waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Nanda Ulfa Khaira; Muhammad Syukran; Ahmad Sazali A. Sitorus; Cut Tria Aswina; Putri Khairani Amalia Siregar; Muhammad Nasir; Nur Fadli; Martin Wilkes; Mohd Nor Siti-Azizah; et al. (Zoologischer Anzeiger, 2025)

Molecular taxonomy of bumblebee gobies (Oxudercidae: Gobionellinae: Brachygobius) in Peninsular Malaysia - Nur Liyana Binti Khairul Yusri; Jamsari Amirul Firdaus Jamaluddin; Abdullah Halim Muhammad-Rasul; Mohd Lokman Ilham-Norhakim; Sahat Ratmuangkhwang; Sébastien Lavoué (Zoologischer Anzeiger, 2025)

Development and characterization of Zingiber zerumbet rhizome crude extract-loaded nanoemulsions: In vitro release and cytotoxicity assessment against MDA-MB-231 breast cancer cell line - Zahra Sanaimehr; Norazlinaliza Salim; Emilia Abdulmalek; Intan Nur Fatiha Shafie; Muhammad Alif Mohammad Latif; Renny Apriliana M. Ansori; Sharida Fakurazi (South African Journal of Botany, 2025)

Lithofacies and juvenile clast variations at Ranu Grati Maar, East Java: Insights into eruptive transitions in monogenetic volcanoes - Muhammad Andriansyah Gurusinga; Mirzam Abdurrachman; Tsukasa Ohba; Takashi Hoshide; Wildan Nur Hamzah; Idham Andri Kurniawan (Journal of Volcanology and Geothermal Research, 2025)

Interfacial defect mitigation in HJT bottom cells for improved efficiency of monolithic perovskite/Si tandem solar cells - Mengmeng Chu; Hasnain Yousuf; Shanshan Gao; Maha Nur Aida; Xiaobo Wang; Muhammad Quddamah Khokhar; Junsin Yi (Chemical Engineering Journal, 2025)

Advancement in hydrogen production, application and strategy towards sustainable energy: Malaysian case study - Mariam Ameen; Huei Yeong Lim; Haswin Kaur; Nur’aini Raman Yusuf; David Onoja Patrick; Muhammad Shahbaz; Abrar Inayat; Suzana Yusup (Process Safety and Environmental Protection, 2025)

Recent strategy on green synthesis of mesoporous silica from waste for a sustainable and circular economy - Reva Edra Nugraha; Nur Aini Fauziyah; Silvana Dwi Nurherdiana; A.R. Yelvia Sunarti; Abdul Aziz; Ni Ketut Sari; Ajit K. Sarmah; Muhammad Al Muttaqii; Zuhriah Mumtazah; Novia Amalia Sholeha; Hasliza Bahruji; Aishah Abdul Jalil; et al. (Journal of Environmental Chemical Engineering, 2025)

Mechanistic insights of facile synthesized-solar driven TiO2 intercalated 2D molybdenum disulfide evaporator for one-pot clean water production - Nurul Syazana Fuzil; Nur Hashimah Alias; Nur Hidayati Othman; Muhammad Shafiq Mat Shayuti; Norazah Abd Rahman; Zulkifli Abdul Rashid; Ahmad Fauzi Ismail; Anwar Ul-Hamid; Izumi Ichinose (Desalination, 2025)

Molecular cloning and modelling of a thermostable α-amylase from a thermophilic Geobacillus sp. DS3 - Lucia Dhiantika Witasari; Leon Bhagawanta Cahyono; Dina Clarissa Kurniawan; Rohmad Yudi Utomo; Muhammad Nur Cahyanto; Muhammad Saifur Rohman; Irfan Dwidya Prijambada (Biotechnology Letters, 2025)

Persicaria minor F-box protein, PmFBK2 targeted by miR156a in response to MeJA treatment, potentially affects stress-related proteins - Nur-Athirah Abd-Hamid; Muhammad-Izzat Ahmad-Fauzi; Ismanizan Ismail (Journal of Plant Physiology, 2025)

Hydropuntia edulis extract mitigates metabolic dysregulation via DPP-4 inhibition, lipid modulation, and GLP-1/AKT1 pathway activation - Maghfirah Savitri; Trina Ekawati Tallei; Ahmad Akroman Adam; Nur Balqis Maulydia; Fatimawali Fatimawali; Gadis Sabrina Tanjung; Muhammad Firdaus; Rony Abdi Syahputra; Fahrul Nurkolis (Food Bioscience, 2025)

Valorization of oil palm Biomass: Investigating ChCl:Lactic Acid deep eutectic solvents for efficient furfural production - Muhammad Fakhrul Syakir Bahazin; Nur Ismah Amalin Mohd Isa; Nur Anis Natasha Mohd Azlan; Mohd Razealy Anuar; Khairul Faizal Pa'ee; Tau-Len Kelly Yong (Biomass and Bioenergy, 2025)

Multi-centric clinical implementation of the remote and automated quality control programme for digital imaging in Malaysia: challenges and pitfalls - Vinoshah S. Ravichandran; Nur Ammi Hamzah; Li Kuo Tan; Virginia Tsapaki; Olivera Ciraj Bjelac; Noramaliza Mohd Noor; Nur Syahiirah Mohamad Mokhtar; Nur Hasyimah Abd Rashid; Adiela Saiful Fazad; Nur Hafizah Zakaria; Siti Norsyafiqah Mohd Mystafa; Wan Nur Ain Wan Ghazali; et al. (Physical and Engineering Sciences in Medicine, 2025)

High genetic diversity and panmictic population of Malabar trevally (Platycaranx malabaricus) - Nuralif Fakhrullah Mohd Nur; Nur Izzati Zulaidi; Muhammad Hanif Fadzli; Min Pau Tan; Siti Azizah Mohd Nor; Ying Giat Seah; Ahasan Habib; Tun Nurul Aimi Mat Jaafar (Marine Biology, 2025)

Putrescine Detection Via PMMA-Zinc(II) Complex Optical Chemosensor: Meat Spoilage Screening Tool - Muhammad Ameerullah Sahudin; Jian Xiong Tan; Khairun Nasriah Azmi; Nur Afny Suhaimi; Shameer Hisham; Nor Kartini Abu Bakar; Muhammad Nidzhom Zainol Abidin; Khairul Anwar Ishak; Nurul Huda Abd Karim (Journal of Fluorescence, 2025)

Insights into the adsorption of ibuprofen onto polyethylene microplastics using molecular dynamic simulation - Muhammad Ikhwan Nizam; Nurfarwizah Adzuan Hafiz; Mohamed Syazwan Osman; Mohamad Syafiq Abdul Wahab; Lei Wang; Noor Fitrah Abu Bakar; Mohamed Hasaan Hussain; Nur Lina Syahirah Mustapa; Chongqing Wang (Journal of Environmental Management, 2025)

Exploring the complex nexus of climate change, food security, and public health: A scientific perspective through bibliometric analysis - Nurul Izzati Mohd Ali; Nur Syamimi Mohamad; Nurul Izzaty Hassan; Zein Kallas; Muhammad Adzran Che Mustapa; Kuok Choy Lam; Kadaruddin Aiyub; Sharif Shofirun Sharif Ali; Najwa Imani Mohd Ali (Environmental Science & Policy, 2025)

Advancing comfort and efficiency: Radiant heating and cooling systems for sustainable architecture - Tarek Abedin; Md Mahfuzur Rahman; Zihad Hasan Joy; Khaled Alnamasi; Irfan Anjum Badruddin; Muhammad Nasir Bashir; Mohammad Nur-E-Alam (Building and Environment, 2025)

Multi-strain Native Probiotics from the Asian Stinging Catfish (Heteropneustes fossilis) Enhance Growth, Blood Health, and Organ Morphology in the Host - Sadia Nusrat Sharna; Kaniz Fatema Nur; Atiqur Rahman; Nittyananda Chandra Das; Jesmin Akter; Mst. Halima Khatun; Sara Momtaj Chowdhury; S. M. Majharul Islam; Muhammad Tofazzal Hossain; Mahbubul Pratik Siddique; M Kabir Hossain; Mohd Golam Quader Khan; et al. (Probiotics and Antimicrobial Proteins, 2025)

Thermal-hydraulics performance and stability two-phase flow using Al2O3 nanofluids in an open natural circulation loop - Dwi Yuliaji; Roy Waluyo; Gatot Eka Pramono; Muhammad Ganjar Putra; Nur Rochman Budiyanto; Shendy Akbar Mariadi; Sunandi Kharisma; Ryan Oktaviandi; Deendarlianto; Indarto; Mulya Juarsa (Annals of Nuclear Energy, 2025)

Establishment and characterization of a novel patient-derived TP63-rearranged anaplastic large-cell lymphoma model PTCL-S1 - Kelila Xin Ye Chai; Elizabeth Chun Yong Lee; Zhimei Li; Nur Ayuni Binte Muhammad; Jing Quan Lim; Dachuan Huang; Soon Thye Lim; Jason Yongsheng Chan; Choon Kiat Ong (Human Cell, 2025)
Anaplastic large-cell lymphoma (ALCL) accounts for 15% of all peripheral T-cell lymphomas globally and can be further divided into subcategories, of which patients with ALK-negative ALCL have dismal prognosis and overall survival. We established a patient-derived xenograft (PDX) and in vitro model (designated PTCL-S1) of TP63 -rearranged ALK-negative ALCL from the primary tumour site of a 55-year old Chinese woman. Whole genome sequencing of the patient’s tumour identified various mutations including AKT1 and NOTCH1 , as well as the TP63 - TBL1XR1 gene fusion. RNA sequencing followed by Sanger sequencing confirmed the gene rearrangement in original tumour, PDX and PTCL-S1 cell line. Immunohistochemistry profiling of the PDX model and cell-line were consistent with the patient’s primary tumour sample (CD3 + /CD30 + /CD79a-). Cytotoxic agents (doxorubicin, etoposide and gemcitabine) commonly used in ALCL treatment exhibited potent anti-proliferative activity in the cell-line. In conclusion, the established PTCL-S1 cell line can be a useful tool for further investigation of the understanding of TP63 -rearranged ALK-negative ALCL.

Emulsifier-free B50 biodiesel-water-ethanol emulsion fuel: A study on combustion characteristics, fuel performance, and emissions - Muhammad Adib Abdul Rashid; Ahmad Muhsin Ithnin; Wira Jazair Yahya; Wan Nur Izzati Wan Mahdi; Nurul Aiyshah Mazlan; Abdullah Aiman Zulmajdi; Dhani Avianto Sugeng; Kinoshita Eiji (Fuel, 2025)

Parity and breastfeeding are contributing factors for geographical differences in breast cancer risk - Boon Hong Ang; Shivaani Mariapun; Farahida Mohd Farid; Imelda Suhanti Ishak; Muhammad Faiz Md Taib; Asfarina Ab Rahim; Lenjai Anak Jembai; Tania Islam; Kartini Rahmat; Farhana Fadzli; Nur Aishah Mohd Taib; Cheng Har Yip; et al. (Cancer Causes & Control, 2025)

Peatland fires in Peninsular Malaysia act as primary source of dioxins, dioxin-like polychlorinated biphenyl, and particulate matter - Ahmad Shalihin Mohd Samin; Nur Batrisyia Hadfina Azmi; Mohd Talib Latif; Yin-Hui Leong; Tengku Sifzizul Tengku Muhammad; Wen Sheng; Norhaniza Amil (Environmental Monitoring and Assessment, 2025)

The effect of chronic microplastic exposure on the growth, biochemical responses, and histological changes of the juvenile sea cucumber Holothuria scabra - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Vijay Subbiah Kumar (Environmental Science and Pollution Research, 2025)
Microplastics (MPs) are minuscule plastic particles less than 5 mm in size, originating from the degradation of larger plastic debris. MPs originate from various sources and pose a significant threat to the marine ecosystem. Holothuria scabra is a species of sea cucumber with high commercial value and among the organisms affected by MPs pollution. H. scabra are also crucial in maintaining a clean seabed and recycling nutrients in the ocean ecosystem. Polymethymethacrylate (PMMA), a durable and transparent plastic polymer widely used as a glass alternative in maritime and other industries. This research aimed to investigate the toxicity effects of polymethylmethacrylate-MPs on the well-being of juvenile sea cucumber H. scabra . Over a 60-day treatment period, polymethylmethacrylate MPs were exposed to the juvenile sea cucumber diet at concentrations of 0.6 MPs/g (Treatment 1), 1.2 MPs/g (Treatment 2), and 10 MPs/g (Treatment 3) while a control group which received no MPs exposure to observe changes in their growth, biochemical responses, and histological alteration. The mean weight, weight gain percentage and specific growth rate exhibited significant differences ( p < 0.05) with the control group displaying the highest SGR value of 1.22 ± 0.35%. Mortality was observed in treatment 2 and 3, respectively. A disruption in enzyme activity was also observed across all treatment groups ( p < 0.05). The findings of growth rates and biochemical responses were further supported by histological observation, uncovering injuries and loss of cellular components in respiratory trees and intestines. This study enhances our understanding of the toxicity mechanism associated with PMMA-MPs in deposit feeder organisms.

Fermented spent coffee ground in African catfish (Clarias gariepinus) diets: Effects on growth performance, digestive enzyme, protein digestibility, amino acid profile, and immune-related gene - Nurdiyana Aqilah Roslan; Zulhisyam Abdul Kari; Suniza Anis Mohamad Sukri; Martina Irwan Khoo; Nani Izreen Mohd Sani; Roslina Rashid; Muhammad Anamul Kabir; Shishir Kumar Nandi; Nik Nur Azwanida Zakaria; Koushik Ghosh; Hasnita Che Harun; El-Sayed Hemdan Eissa (Aquaculture, 2025)

Spatial variation of crustal anisotropy in Simeulue Island, Indonesia, from shear wave splitting analysis - Syuhada Syuhada; Faiz Muttaqy; Titi Anggono; Bayu Pranata; Nanang T. Puspito; Mohamad Ramdhan; Febty Febriani; Muhammad Ma'ruf Mukti; Cinantya Nirmala Dewi; Mohammad Hasib; Aditya Dwi Prasetio; Atin Nur Aulia; et al. (Physics of the Earth and Planetary Interiors, 2025)

Corrigendum to “Three-layer core-shell Ag/AgCl/PEDOT: PSS composite fibers via a one-step single-nozzle technique enabled skin-inspired tactile sensors” [Chem. Eng. J. 442(Part 2) (2022) 136270] - Yuhang Wang; Jiadeng Zhu; Ming Shen; Chunxia Gao; Peng Wang; Wei Zhou; Chuanyun Zhao; Nur Muhammad; Jiefeng Gao; Qiang Gao (Chemical Engineering Journal, 2025)

Transfersome-based delivery of Muntingia calabura fruit extract for anti-aging applications - Syamsu Nur; Muhammad Fadly Noor Alwani; Fitriyanti Jumaetri Sami; Amriani Sapra; Andi Nur Aisyah; Maulita Indrisari; Nursamsiar; Nurul Arfiyanti Yusuf; Aristianti (Biocatalysis and Agricultural Biotechnology, 2025)

Shark Capture using Small-Scale Longline Drift Fisheries in the Southern Indian Ocean of Java, Indonesia - Yaser Krisnafi; Dian Novianto; Kasim Permana; Ratih Purnama Sari; Muhammad Nur Arkham (Thalassas: An International Journal of Marine Sciences, 2025)

Physiological responses of hybrid grouper (Epinephelus fuscoguttatus X Epinephelus lanceolatus) to temperature fluctuation stress revealed by LCMS/MS-based mucus and sera metabolomics - Ellia Kartini Mujar; Saleema Matusin; Nur Syahirah Yahya; Muhammad Safwan Ahamad Bustamam; Annie Christianus; Khozirah Shaari; Nur Kartinee Kassim; Faridah Abas; Jen Kit Tan; Intan Safinar Ismail (Fish Physiology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Reclaiming Wolffia arrhiza as fish feed for the phytoremediation of aquaculture effluent - Nor Sakinah Mohd Said; Muhammad Zahin Zakaria; Norsyasmin Izzati Samsuddin; Nur Aina'a Zafirah Barom; Navieen AL. M. Murugiah; Siti Rozaimah Sheikh Abdullah (Journal of Environmental Management, 2025)

Assessment of the fit and wearability of commercially available KN95 respirators for children in Indonesia and Nepal - Anne Sleeuwenhoek; Claire J. Horwell; Kusum Shahi; Jihan Nur Azizah; Rabindra Bhandari; William Mueller; Muhammad Iqbal; Meghnath Dhimal; Miranda Loh; Karen S. Galea (International Journal of Hygiene and Environmental Health, 2025)

Development of untypical meteorological year in the hot and humid climate of Indonesia: An application for thermal stress assessment - I Dewa Gede Arya Putra; Hideyo Nimiya; Ardhasena Sopaheluwakan; Tetsu Kubota; Han Soo Lee; Muhammad Nur Fajri Alfata; Donaldi Sukma Permana; Reza Bayu Perdana (Building and Environment, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Recent advances in recycling and upcycling of hazardous plastic waste: A review - Siti Zulaika Khairul Anuar; Abu Hassan Nordin; Siti Muhamad Nur Husna; Abdul Hafidz Yusoff; Syafikah Huda Paiman; Siti Fadilla Md Noor; Muhammad Luqman Nordin; Siti Nurlia Ali; Ya Mohammad Nazir Syah Ismail (Journal of Environmental Management, 2025)

Genetic profile of the whole genome sequence of African swine fever virus from the first outbreak in Malaysian Borneo - Mohammad Masrin Azami; Nur Aimi Syarina Pauzi; Noazlina Hamdan; Muhammad Redzwan Sidik; Aisya Naama Tulis; Roslina Hassan; Faizah Hanim Mohd Saeid (Veterinary Research Communications, 2025)

Evaluation of methoxyflavones as dengue NS2B–NS3 protease inhibitors: an in silico and in vitro studies - Nur Farhana Mustafa; Kian-Kai Cheng; Siti Aisyah Razali; Habibah A. Wahab; Nurul Hanim Salin; Iffah Izzati Zakaria; Muhammad Helmi Nadri (Molecular Diversity, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

The potential of hydrolyzed chicken feather meal as a partial replacement for fish meal and its effects on the growth and health status of African catfish (Clarias gariepinus) fingerlings - Nik Nur Akmal ‘Aliah Abdul Rashid; Zulhisyam Abdul Kari; Parashuram Kallem; Suniza Anis Mohamad Sukri; Syed Muhammad Al-Amsyar; Noor Khalidah Abdul Hamid; Muhammad Anamul Kabir; El-Sayed Hemdan Eissa; Martina Irwan Khoo; Krishnakumar Velayudhannair; Ajay Guru (Aquaculture International, 2025)

Enhancing Efavirenz Bioavailability Via Polymer-Based Buccal Administration: Optimization and Characterization of Nanocrystal-Loaded Dissolving Microneedle Delivery Systems - Khairiyah Khairiyah; Muh. Bisfain Asaf; Nur Afni Annisa Achmad; Rachmatya W. Tuna; Irfan Kurniawan; Anugerah Yaumil Ramadhani Aziz; Maria Mir; Juan Domínguez-Robles; Mónica Millán-Jiménez; Ilyas Essadki-Aittaji; Ana B. Cobo-González; Muhammad Aswad; et al. (The AAPS Journal, 2025)

Impact of Storm Pabuk on a Monsoon Coral Beach: Bidong Island, Terengganu (Malaysia) - Siti Nur Hanani Zainuddin; Che Din Mohd Safuan; Junainah Zakaria; Cherdvong Saengsupavanich; Muhammad Zahir Ramli; Azizi Ali; Zainudin Bachok; Fatihah Shariful; Alya Syakirah Tajul Ariffin; Idham Khalil; Aidy M. Muslim; Hasrizal Shaari; et al. (Marine Geology, 2025)

Comprehensive analysis and human health risk assessment of tap water quality in Dhaka City, Bangladesh: Integrating source identification, index-based evaluation, and heavy metal assessment - Tasrif Nur Ariyan; Shamshad Begum Quraishi; Md. Nur E Alam; Muhammad Shahidur Rahman Khan; Farzana Ferdous Faria; Alamgir Kabir (Journal of Hazardous Materials, 2025)

Continuous forests and non-IBA forest patches provide a safe haven for the tropical bird community in highly fragmented urban landscapes - Sharifah Nur Atikah; Muhammad Syafiq Yahya; Kang Woei Ong; Ruzana Sanusi; Ahmad Razi Norhisham; Badrul Azhar (Biodiversity and Conservation, 2025)

PolarBytes: Advancing polar research with a centralized open-source data sharing platform - Nur Haznirah Hazman; Rohaizaazira Mohd Zawawi; Ainin Sofia Jusoh; Muhammad Akmal Remli; Marieanne Christie Leong; Mohd Saberi Mohamad; Sarahani Harun (Environmental Modelling & Software, 2025)

Spatial modelling of regional drought severity index based on multiple criteria analysis using cloud-based remote sensing data in agriculture land - Khalifah Insan Nur Rahmi; Muhammad Dimyati; Mangapul Parlindungan Tambunan; Jalu Tejo Nugroho (Modeling Earth Systems and Environment, 2025)

Chemical characterization and biological activity investigation of Curculigo orchioides Gaertn. - Tuz Mia Nur Akhi; Irin Sultana; Abdullah Al Faroq; Md. Shimul Bhuia; M. Mohi Uddin Chowdhury; Rafiqul Haider; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Vegetos, 2025)

Evaluation of mechanical responses of asphalt mixtures incorporating plastic waste as additives by different compaction efforts and mixing temperatures for a sustainable mixture - Siti Nur Naqibah Kamarudin; Muhammad Naqiuddin Mohd Warid; Mohd Zul Hanif Mahmud; Haryati Yaacob; Kabiru Usman Rogo; Mohd Khairul Afzan Mohd Lazi (Environmental Science and Pollution Research, 2025)

Elucidation of synbiotic diet comprising of Lactobacillus plantarum L20 and Sargassum polycystum on gastrointestinal microbiota, tissue structures and AHPND associated dysbiosis susceptibility in black tiger shrimp (Penaeus monodon) - Yong Kit Chin; Mohamad Azzam-Sayuti; Aslah Mohamad; Wan Omar Haifa-Haryani; Mohd Ihsanuddin Ahmad; Muhammad Farhan Nazarudin; Nur Shidaa Mohd Ali; Md Yasin Ida-Muryany; Murni Marlina Abd Karim; Salleh Annas; Mohd Nor Norhariani; Mohammad Noor Azmai Amal; et al. (Aquaculture, 2025)

Sorghum starch review: Structural properties, interactions with proteins and polyphenols, and modification of physicochemical properties - Muhammad Luthfan Haziman; Muhammad Iskandar Ishaq; Muhammad Abdillah Hasan Qonit; Endang Gati Lestari; Pepi Nur Susilawati; Wiwi Widarsih; Cheppy Syukur; Heny Herawati; Ramlah Arief; Budi Santosa; Resmayeti Purba; Robi Andoyo; et al. (Food Chemistry, 2025)

Impact of Indonesia's Forest Management Units on the reduction of forest loss and forest fires in Sulawesi - Colas Chervier; Stibniati S. Atmadja; Sandy Nofyanza; Choiriatun Nur Annisa; Fitri Nurfatriani; Rochadi Kristiningrum; Muhammad Alif K. Sahide; Ali Suhardiman; Syukur Umar (Ecological Economics, 2025)

Evaluation of Microplastics Ingested by Sea Cucumber Holothuria Scabra from Pulau Jambongan, Sabah - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Vijay Kumar Subbiah; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Audrey Daning Tuzan; Sitti Raehanah Muhammad Shaleh; Norfazreena Mohd Faudzi; Rossita Shapawi; Muhammad Dawood Shah; Tze Young Thung (Bulletin of Environmental Contamination and Toxicology, 2025)

MicroRNA expression profiling of ovine epithelial cells stimulated with the Staphylococcus aureus in vitro - Ghulam Asghar Sajid; Muhammad Jasim Uddin; Saif Adil Abbood Al-Janabi; Abdiaziz Nur Ibrahim; Mehmet Ulas Cinar (Mammalian Genome, 2024)

Effectiveness of Direct Sulfonated Polysulfone in Dual Chamber Microbial Fuel Cells Based Dewatered Sludge for Power Generation - Kavita Pusphanathan; Muaz Mohd Zaini Makhtar; Hafiza Shukor; Muhammad Najib Ikmal Mohd Sabri; Nur Atiqah Abdul Rasik; Nurul Atiqah Shamsuddin; Masoom Raza Siddiqui; Riti Thapar Kapoor; Mohd Rafatullah (International Journal of Environmental Research, 2024)

Two Strains of Endophytic Bacillus velezensis Carrying Antibiotic-Biosynthetic Genes Show Antibacterial and Antibiofilm Activities Against Methicillin-Resistant Staphylococcus aureus (MRSA) - Jepri Agung Priyanto; Muhammad Eka Prastya; Egiyanti Nur Widhia Hening; Erma Suryanti; Rhesi Kristiana (Indian Journal of Microbiology, 2024)

Monitoring groundwater vulnerability for sustainable water resource management: A DRASTIC-based comparative assessment in a newly township area of Bangladesh - Muhammad Anwar Iqbal; Mohammed Abdus Salam; Md Nur-E-Alam; Nusrat Jahan Rubaida; Hafizur Rahman; Mohammed Faruque Uddin (Groundwater for Sustainable Development, 2024)

Resilience underground: Understanding earthworm biomass responses to land use changes in the tropics - Badrul Azhar; Peter van der Meer; Rutger F. Sterenborg; Muhammad Syafiq Yahya; Norhisham Razi; Maisarah Burhanuddin; Jasmijn Rookmaker; Nur Syarihah Sahimi; Welmoed van der Pal; Frisco Nobilly; Siti Aisyah Mohd Azam; Meriam Ubachs; et al. (Biological Conservation, 2024)

Effects of substitution of crude palm oil with palm-pressed fibre oil on the laying hen’s performance, egg production and egg quality traits - Mookiah Saminathan; Muhammad Amirul Fuat; Wan Nooraida Wan Mohamed; ‘Abidah Md Noh; Nur Atikah Ibrahim (Tropical Animal Health and Production, 2024)

Rare earth metals and minerals industries: status and prospects - Sahupriadi; M Nur Alamsyah Rahman; Muhammad Risal Rusman (International Geology Review, 2024)

Chromium-extracted aluminum catalyst for co-pyrolysis of cotton fabric waste and polypropylene plastic waste to bio-oil - Nur Alwani Ali Bashah; Muhammad Zahiruddin Ramli; Wan Zuraida Wan Kamis; Siti Shawalliah Idris; Mohamad Anuar Kamaruddin; Ahmad Syahir Zulkipli; Moses Aderemi Olutoye (Journal of Environmental Chemical Engineering, 2024)

An efficient zero-labeling segmentation approach for pest monitoring on smartphone-based images - L. Minh Dang; Sufyan Danish; Asma Khan; Nur Alam; Muhammad Fayaz; Dinh Khuong Nguyen; Hyoung-Kyu Song; Hyeonjoon Moon (European Journal of Agronomy, 2024)

Economic value of mangrove ecosystem services in the coastal area of Bintan Island, Indonesia - Muhammad Nur Arkham; Septa Riadi; Yudi Wahyudin; Yaser Krisnafi (Wetlands Ecology and Management, 2024)

Fine-tuning plant valuable secondary metabolite biosynthesis via small RNA manipulation: strategies and potential - Nur Irdina Izzatie Mohd Zahid; Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Ismanizan Ismail; Muhamad Hafiz Che-Othman (Planta, 2024)

Design anticancer potential of Zn(II)isoleucinedithiocarbamate complex on MCF-7 cell lines: synthesis, characterization, molecular docking, molecular dynamic, ADMET, and in-vitro studies - Rizal Irfandi; Indah Raya; Ahyar Ahmad; Ahmad Fudholi; Riswandi; Santi Santi; Wynda Puspa Azalea; Suriati Eka Putri; Muhammad Nur Alam; Unang Supratman; Samuel Olawale Olubode; Eid A. Abdalrazaq; et al. (Molecular Diversity, 2024)

Photocatalytic degradation of rhodamine B dye pollutants by Fe3O4/SiO2 core–shell magnetic nanocomposite functionalized with TiO2 - Maisari Utami; Aditya Rianjanu; Muhammad Miqdam Musawwa; Selfi Citra Nur; Puji Lestari; Fatimah S. Al-Khattaf; Ashraf Atef Hatamleh; Murugesan Chandrasekaran; Woo Jin Chung; Soon Woong Chang; Balasubramani Ravindran (Environmental Geochemistry and Health, 2024)

Assessing Trace Metal-Based Human Health Risks for Commonly Used Body Soaps in Bangladesh - Ashraful Hoque; Taznova Anwar Tanbi; Nakshi Saha; Sabbir Howlader; Nobonita Sarker; Aminul Islam Chowdhury; Amitava Bandyopadhyay; Shahidul Islam; Muhammad Abu Bakar; Nur E. Alam; Ashok Kumar Chakraborty; Sumon Ganguli (Biological Trace Element Research, 2024)

Innovative solutions for the removal of emerging microplastics from water by utilizing advanced techniques - Noornama; Muhammad Nidzhom Zainol Abidin; Nor Kartini Abu Bakar; Nur Awanis Hashim (Marine Pollution Bulletin, 2024)

In-depth analysis of ambient air pollution changes due to the COVID-19 pandemic in the Asian Monsoon region - Mohd Talib Latif; Noorain Purhanudin; Nur Zulaikha Mohd Afandi; Maria Obiminda L. Cambaliza; Nor Diana Abdul Halim; Nor Syamimi Sufiera Limi Hawari; To Thi Hien; Ohnmar May Tin Hlaing; Warnakulasuriya Roshani Loreta Hiranthi Jansz; Muhammad Fahim Khokhar; Puji Lestari; Shih-Chun Candice Lung; et al. (Science of The Total Environment, 2024)

The first outbreak of Lumpy Skin Disease in Indonesia - Widi Nugroho; Hani Muhamad Mardani; Michael Philipp Reichel; Yul Fitria; Yuli Miswati; Niko Febrianto; Muhammad Edy Nuryanto; Intan Apriana; Nur Azzahrawani; Eno Martalina; Shelly Kusumarini; Hermanto; et al. (Tropical Animal Health and Production, 2024)

Performance test of clean-coastal-water composite sentinel 2A image for shallow water bathymetry mapping - Munawaroh Munawaroh; Pramaditya Wicaksono; Nur Mohammad Farda; Yustisi Lumban-Gaol; Nurul Khakhim; Muhammad Kamal (Remote Sensing Applications: Society and Environment, 2024)

Deep eutectic solvents as sustainable extraction media for extraction of polysaccharides from natural sources: Status, challenges and prospects - Noorfatimah Yahaya; Ahmad Husaini Mohamed; Muhammad Sajid; Nur Nadhirah Mohamad Zain; Pao-Chi Liao; Kit Wayne Chew (Carbohydrate Polymers, 2024)

On the versatility of graphene-cellulose composites: An overview and bibliometric assessment - Nur Faraliana Japri; Zaiton Abdul Majid; S.K. Ghoshal; Wan Hazman Danial; Hong Heng See; Muhammad Zamir Othman (Carbohydrate Polymers, 2024)

A deep learning-based theoretical protocol to identify potentially isoform-selective PI3Kα inhibitors - Muhammad Shafiq; Zaid Anis Sherwani; Mamona Mushtaq; Mohammad Nur-e-Alam; Aftab Ahmad; Zaheer Ul-Haq (Molecular Diversity, 2024)

In vivo assessment of Lactobacillus plantarum strains in black tiger shrimp (Penaeus monodon): implications for growth performance, probiotic-pathogen interaction, and defense against AHPND infection - Yong Kit Chin; Wan Omar Haifa-Haryani; Muhammad Farhan Nazarudin; Mohd Ihsanuddin Ahmad; Mohamad Azzam-Sayuti; Nur Shidda Mohd Ali; Mohamad Syazwan Ngalimat; Aslah Mohamad; Md Yasin Ida-Muryany; Murni Karim; Annas Salleh; Mohd Nor Norhariani; et al. (Aquaculture International, 2024)

Unveiling the unique potential of MXene with and without graphene nanoplatelet for thermal energy storage applications - Amirul Aminur Rashid; Muhammad Syahir Mansor; Nur Awanis Hashim; Sona R. Moharir; Norhuda Abdul Manaf (Environmental Science and Pollution Research, 2024)

Dual adoption opportunities and prospects for mining and industrial waste recovery through an integrated carbon capture, utilization and storage - Faradiella Mohd Kusin; Sharifah Nur Munirah Syed Hasan; Verma Loretta M. Molahid; Muhammad Hameer Soomro (Sustainable Production and Consumption, 2024)

Characterization of the future northeast monsoon rainfall based on the clustered climate zone under CMIP6 in Peninsular Malaysia - Zulfaqar Sa'adi; Nor Eliza Alias; Zulkifli Yusop; Mohammed Magdy Hamed; Prabhakar Shukla; Mohamad Rajab Houmsi; Nur Athirah Mohamad; Mohammed Sanusi Shiru; Nurzalikha Sa'adi; Mohd Khairul Idlan Muhammad; Zafar Iqbal; Umer Jeelanie Banday (Atmospheric Research, 2024)

Deep learning and LiDAR integration for surveillance camera-based river water level monitoring in flood applications - Nur Atirah Muhadi; Ahmad Fikri Abdullah; Siti Khairunniza Bejo; Muhammad Razif Mahadi; Ana Mijic; Zoran Vojinovic (Natural Hazards, 2024)

Spatial distribution of heavy metal abundance at distance gradients of roadside agricultural soil from the busiest highway in Bangladesh: A multi-index integration approach - Md. Saydul Islam; Md. Nur-E-Alam; Muhammad Anwar Iqbal; Md. Badiuzzaman Khan; Shamim Al Mamun; Md. Yunus Miah; Md. Rasheduzzaman; S. Appalasamy; Mohammed Abdus Salam (Environmental Research, 2024)

Characterization of Active Coagulant Agent from Crude and Extracted Stem of Musa for Treating Food Processing Wastewater - Muhammad Burhanuddin Bahrodin; Nur Syamimi Zaidi; Loh Zhang Zhan; Norelyza Hussein; Abudukeremu Kadier; Achmad Syafiuddin; Ayman A. Ghfar; Muhammad Aamer Mehmood (Water, Air, & Soil Pollution, 2024)

Employing gridded-based dataset for heatwave assessment and future projection in Peninsular Malaysia - Zulfaqar Sa’adi; Mohammed Magdy Hamed; Mohd Khairul Idlan Muhammad; Ming Fai Chow; Nur Athirah Mohamad; Mohd Hadi Akbar Basri; Mohamad Faizal Ahmad; Nurzalikha Sa’adi; Nor Eliza Alias; Zulkifli Yusop; Mohamad Rajab Houmsi; Prabhakar Shukla; et al. (Theoretical and Applied Climatology, 2024)

Growth Patterns, Condition Factor, and Population Dynamics of Snapper Lutjanus bengalensis and Lutjanus lutjanus (Pisces: Lutjanidae) Harvested from Aceh Waters Indonesia - Sri Riska Rahayu; Syamsul Rizal; Nur Fadli; Ilham Raza; Muhammad Isran Lazuardi; Luvi Syafrida Handayani; Nanda Muhammad Razi; Martin Wilkes; Mohd Nor Siti-Azizah; Zainal A. Muchlisin (Thalassas: An International Journal of Marine Sciences, 2024)

Nutritional and health promoting perspectives of Monostroma spp. (Chlorophyta): A systematic review - Sana Mansoor; Khawaja Muhammad Imran Bashir; Md. Mohibbullah; Maria Dyah Nur Meinita; Mohammed Nurul Absar Khan; Jae-Hak Sohn; Jae-Suk Choi (Journal of Applied Phycology, 2024)

Multi-omics tools for understanding Trichoderma-plant symbiosis: biotechnological developments and future directions - Nur Syafikah Abdullah; Febri Doni; Muhammad Adil Awal; Muhamad Shakirin Mispan; Mohd Zuwairi Saiman; Yusmin Mohd-Yusuf; Nurul Shamsinah Mohd Suhaimi (Symbiosis, 2024)

A control rod worth prediction using Adaptive Neuro-Fuzzy Inference System for Pre-Calibration Method at TRIGA PUSPATI Reactor - Teh Zhi Hui; Nur Syazwani Mohd Ali; Mohd Sabri Minhat; Jasman Zainal; Muhammad Arif Sazali; Muhammad Syahir Sarkawi; Khairulnadzmi Jamaluddin; Nor Afifah Basri; Mohsin Mohd Sies; Nahrul Khair Alang Md Rashid (Annals of Nuclear Energy, 2024)

Reusable adsorbent of magnetite in mesoporous carbon for antibiotic removal - Teguh Ariyanto; Nova Yoga Pradana; Muhammad Hafish Nur Saif; Bagus Adjie Prasetyo; Imam Prasetyo; Macarena Munoz (Environmental Science and Pollution Research, 2024)

Poly-(ionic liquid) coated with magnetic nanoparticles for micro solid phase extraction of polycyclic aromatic hydrocarbons in food samples - Faizah Muhammad Yunus; Yatimah Alias; Noorfatimah Yahya; Nur Nadhirah Mohamad Zain; Muggundha Raoov (Food Additives & Contaminants: Part A, 2024)

Selective Delivery of Clindamycin Using a Combination of Bacterially Sensitive Microparticle and Separable Effervescent Microarray Patch on Bacteria Causing Diabetic Foot Infection - Nurul Fauziah; Nur Annisa Safirah; Iis Nurul Rahmadani; Muhammad Nur Hidayat; Nur Azizah Fadhilah; Nana Juniarti Natsir Djide; Andi Dian Permana (Pharmaceutical Research, 2024)

Molybdenum oxide-based catalyst towards better hydrogen production: effects of isothermal carburization - Mohd Nor Latif; Nur Syakirah Abdul Rahim; Salma Samidin; Siti Hasnawati Jamal; Muhammad Rahimi Yusop; Wan Nor Roslam Wan Isahak; Alinda Samsuri (Environmental Science and Pollution Research, 2024)

Utilizing a Low-Cost Air Quality Sensor: Assessing Air Pollutant Concentrations and Risks Using Low-Cost Sensors in Selangor, Malaysia - Zaki Khaslan; Mohd Shahrul Mohd Nadzir; Hamimatunnisa Johar; Zhang Siqi; Nor Azura Sulong; Faizal Mohamed; Shubhankar Majumdar; Fatin Nur Afiqah Suris; Nor Syamimi Sufiera Limi Hawari; Jintu Borah; Maggie Ooi Chel Gee; Muhammad Ikram A. Wahab; et al. (Water, Air, & Soil Pollution, 2024)

Current state, strategies, and perspectives in enhancing artemisinin production - Ali Muhammad Zakariya; Mohd Zuwairi Saiman; Henrik Toft Simonsen; Nur Kusaira Khairul Ikram (Phytochemistry Reviews, 2024)

Potential application of 2D nano-layered MXene in analysing and remediating endocrine disruptor compounds and heavy metals in water - Muhammad Nur’ Hafiz Rozaini; Kuan Shiong Khoo; Muhammad Amirul Aizat Mohd Abdah; Baranitharan Ethiraj; Mohammad Mahtab Alam; Aliya Fathima Anwar; Normawati M. Yunus; Chin Seng Liew; Jun Wei Lim; Chii-Dong Ho; Woei-Yenn Tong (Environmental Geochemistry and Health, 2024)

Emerging patterns of genetic diversity in the critically endangered Malayan tiger (Panthera tigris jacksoni) - Kate Allberry; Jeffrine Japning Rovie-Ryan; Nur Alizati Nabila Giarat Ali; Nurul-Ain Elias; Mark Rayan Darmaraj; Christopher Chai Thiam Wong; Lau Ching Fong; Olutolani Smith; Khairul Amirin Bin Mohamed; Mohamad Izereen Bin Amat Mukri; Muhammad Hafiz Bin Mohd Yazid; Matthew J. Struebig; et al. (Biodiversity and Conservation, 2024)
Southeast Asia experiences some of the highest deforestation in the world. Loss of tropical forest typically leads to widespread habitat fragmentation, with detrimental effects on dispersal ability and gene flow—particularly for large carnivores. We conducted mtDNA and microsatellite analysis to assess—for the first time—contemporary patterns of genetic diversity in the Malayan tiger. We collected 295 suspected carnivore samples in Peninsular Malaysia, from which we identified 26 as originating from tiger using 16 polymorphic microsatellite loci, comprising 22 individual tigers. Despite limitations of the study, our findings suggest tiger subpopulations in the north of the peninsula maintain some genetic connectivity and migration between two putative geographic subpopulations in the Main Range and Greater Taman Negara, with negligible population segregation due to dispersal barriers such as road infrastructure. We identified consistently lower levels of genetic diversity in tigers in the Greater Taman Negara region compared to tigers in the Main Range and small but emerging differences in nuclear and mitochondrial genetic diversity. Our mtDNA haplotype and nuclear DNA analyses suggest the levels of genetic diversity in Malayan tigers may be amongst some of the lowest of the surviving tiger subspecies, though the study is limited both in scale and genomic loci. Our findings are consistent with an expected lag between the rapid decline of tigers in Peninsular Malaysia by over 95% in the last 70 years and observed differences in their levels of genetic diversity.

Interspecific hybridization of decapod crustacean species with commercial interest—A review - Muhammad Nur Syafaat; Muyassar H. Abualreesh; Norhafiza Ilyana Yatim; Hanafiah Fazhan; Khor Waiho; Hongyu Ma; Victor Tosin Okomoda; Mhd Ikhwanuddin (Reviews in Aquaculture, 2024)
Interspecies hybridization has been widely used in the development of aquaculture in fish species but there is not much impact in crustacean species. Several species of crustaceans that have been successfully crossed still have low hatching rates and the hybrids obtained have not met expectations. This review tries to summarize and analyse interspecific hybridization of cultured crustacean species (shrimps, lobsters, crayfish and crabs) and its potential for development of crustacean aquaculture production. The success of cross‐breeding on several species of shrimp and lobster has been supported by artificial insemination technology. In crabs, artificial insemination cannot be applied and cross‐breeding still relies on natural mating with an unstable success rate. In addition to cross‐breeding in captivity, cross‐breeding of crustacean species (shrimp, lobster, crayfish and crab) in nature has also been found. Interbreeding of crustacean species in nature cannot always be distinguished morphologically, hybrids between them can be known with certainty after carrying out molecular analysis. Even though the level of reproductive performance in cross‐breeding of shrimp, lobster, crayfish and crab species is still low, cross‐breeding efforts must be continued to obtain more information so that it can later be mapped which species have the potential to develop hybrids for cultivation. Furthermore, growth, reproductive performance, monosex hybridity and disease resistance are all hybrid parameters that must be evaluated.

Evaluation of the microplastics in bivalves and water column at Pantai Teluk Likas, North Borneo, Malaysia - Nur Nashrah Abd Rahman; Nurzafirah Mazlan; Sarah Syazwani Shukhairi; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Haniza Harun; Afaf Baktir (Environmental Science and Pollution Research, 2024)

In silico characterization of GbPAL, GbCHS, GbDFR and GbANS structural genes involved in the biosynthesis of flavonoids in Gynura bicolor DC - Nurul Jadid; Muhammad Rifqi Nur Ramadani; Aulia Febrianti Widodo; Noor Nailis Sa'adah; Dini Ermavitalini; Maulidia Rahmawati; Septi Anita Sari; Iro Datus Soleha; Faisol Mas'ud (South African Journal of Botany, 2024)

Unlocking the potential of Garcinia atroviridis fruit polysaccharides: A synergistic approach for obesity and hypertension management - Nur Qistina Abdul Razak; Chee-Yuen Gan; Muhammad Hakimin Shafie (Food Bioscience, 2024)

Chemical characterization and biological activity of Molineria latifolia root extract as dermal antiaging: Isolation of natural compounds, in silico and in vitro study - Syamsu Nur; Muhammad Hanafi; Heri Setiawan; Berna Elya (Biocatalysis and Agricultural Biotechnology, 2024)

Ultrafiltration membrane fabricated from polyethylene terephthalate plastic waste for treating microalgal wastewater and reusing for microalgal cultivation - Hemamalini Rawindran; Nur Arif bin Hut; Dhita Karunia Vrasna; Pei Sean Goh; Jun Wei Lim; Chin Seng Liew; Chii-Dong Ho; Hooi-Siang Kang; Muhammad Kashif Shahid; Hui-Suan Ng; Mohamed A. Habila; Kuan Shiong Khoo (Chemosphere, 2024)

Simultaneous nitrification and denitrification of real domestic wastewater using novel biodegradable Cocos Nucifera fibre as biofilter media and carbon source: Performances and microbial community composition - Zhang Zhan Loh; Nur Syamimi Zaidi; Ee Ling Yong; Muhammad Burhanuddin Bahrodin; Azmi Aris (Journal of Water Process Engineering, 2024)

Revolutionizing wastewater treatment with microalgae: Unveiling resource recovery, mechanisms, challenges, and future possibilities - Hassimi Abu Hasan; Mohd Hafizuddin Muhamad; Bin Ji; Nur Aisyah Nazairi; Koh Weng Jiat; Saffi Irdina Sim Wan Azlan Sim; Amir Fitri Muhammad Shafiq Poh (Ecological Engineering, 2023)

Network analysis reveals overlapping roles of stakeholders related to seagrass-data provisioning in Indonesia - Nurul Dhewani Mirah Sjafrie; Pramaditya Wicaksono; Udhi E. Hernawan; Triyono; Doddy M. Yuwono; Muhammad Hafizt; Novi Susetyo Adi; Rohani Ambo-Rappe; Bayu Prayudha; Muhammad Banda Selamat; Sofia Yunia Sani; Setiawan Djody Harahap; et al. (Marine Policy, 2023)

Morphometric and genetic variations of three grouper species (genus Epinephelus) from the northern region of Aceh province, Indonesia - Nur Fadli; Adrian Damora; Zainal Abidin Muchlisin; Mutia Ramadhaniaty; Nanda Muhammad Razi; Sri Riska Rahayu; Edison D. Macusi; Ahasan Habib; Mohd N. Siti-Azizah (Zoologischer Anzeiger, 2023)

RETRACTED: Effects of dumpsite leachate plumes on surface and groundwater and the possible public health risks - Joseph Omeiza Alao; Abubakar Fahad; Hazem Ghassan Abdo; Daniel A. Ayejoto; Hussin Almohamad; Muhammad Sani Ahmad; Mohammed Shettima Nur; Theophilus Toro Danjuma; Mumeen Adebayo Yusuf; Olaleye Timilehin Francis; Alao Ovaioza Joy (Science of The Total Environment, 2023)

Antioxidant and antimicrobial activities of essential oils extracted from bamboo (Bambusa vulgaris) leaves and its application in skincare products: A review - Abu Hurairah Darwisy Alias; Nur Qistina Abdul Razak; Muhammad Hasnun Md Yusoff; Kian-Hui Chin; Mohd Lias Kamal; Noor Hafizah Uyup; Shafinas Abdullah; Nur Syuhada Ridzuan; Mardiana Saaid; Muhammad Hakimin Shafie (Biocatalysis and Agricultural Biotechnology, 2023)

Length Frequency Distribution, Length-Weight Relationships and Growth Parameters of Coastal Trevally Turrum coeruleopinnatum (Rüppell, 1830) Caught from Terengganu Waters, Malaysia - Muhammad Hanif Fadzli; Tun Nurul Aimi Mat Jaafar; Ahmad Shaqiq Alizdi Ahmad Sharikin; Tan Min Pau; Nur Athirah Abd Latiff; Siti Asmal Mat Piah; Rumeaida Mat Piah (Thalassas: An International Journal of Marine Sciences, 2023)

Synthesis of ethyl levulinate over sulfonated lignin-based carbon catalyst as a fuel additive to biodiesel-diesel blends towards engine emissions - Abdull Hafidz Hassan; Muzakkir Mohammad Zainol; Muhammad Alif Samion; Muhammad A`qil Azlan; Mohd Asmadi; Ahmad Rafizan Mohamad Daud; Idris Saad; Nur Aina Najwa Mohd Nor Azman (Journal of Cleaner Production, 2023)

Peatland plants growth performance of valorized oil palm microfibers infiltrated in chitosan/NPK and chitosan/PMAA/NPK composite - Adisti Permatasari Putri Hartoyo; Fauzan Aulia; Dimas Nur Muhammad; Evi Puspitasari; Yudi Setiawan; Dede J. Sudrajat; Hilmi Naufal; Anne Carolina; Achmad Solikhin (Bioresource Technology Reports, 2023)

Current status and future prospects of simultaneous nitrification and denitrification in wastewater treatment: A bibliometric review - Zhang Zhan Loh; Nur Syamimi Zaidi; Achmad Syafiuddin; Ee Ling Yong; Muhammad Burhanuddin Bahrodin; Azmi Aris; Raj Boopathy (Bioresource Technology Reports, 2023)

Identifying indicator bird species for sustainable oil palm plantation certification - Zulkifli Nursyamin; Muhammad Syafiq Yahya; Sharifah Nur Atikah; Kamil Azmi Tohiran; Ahmad R. Norhisham; Nurul Wahida Othman; Alex M. Lechner; Badrul Azhar (Journal of Cleaner Production, 2023)

Do silvopastoral management practices affect biological pest control in oil palm plantations? - Frisco Nobilly; Sharifah Nur Atikah; Muhammad Syafiq Yahya; Shokri Jusoh; Thomas M. R. Maxwell; Ahmad Razi Norhisham; Kamil Azmi Tohiran; Raja Zulkifli; Badrul Azhar (BioControl, 2023)

Progress in the utilization of water hyacinth as effective biomass material - Asep Bayu Dani Nandiyanto; Risti Ragadhita; Siti Nur Hofifah; Dwi Fitria Al Husaeni; Dwi Novia Al Husaeni; Meli Fiandini; Senny Luckiardi; Eddy Soeryanto Soegoto; Arif Darmawan; Muhammad Aziz (Environment, Development and Sustainability, 2023)
Water hyacinth ( Eichhornia crassipes ) is considered a prospective free-floating aquatic plant potentially used to address current issues on food, energy, and the environment. It can grow quickly and easily in various tropical and subtropical environments as long as it has access to adequate light and water to support photosynthetic growth. Ecosystems are threatened by their invasive growth and remarkable capacity for adaptation. However, managing this plant can result in valuable products. This paper demonstrates particle technologies that might be used to utilize water hyacinths, including brake pads, fertilizer, bioenergy, animal feed, phytoremediation agents, bioplastics, and adsorbents. This study is accompanied by a discussion based on the conducted experiments and currently available literature, providing readers with a clearer understanding. Water hyacinth's capacity to absorb macro- and micro-nutrients, nitrogen, and phosphorus makes it a good plant for phytoremediation. The prospect of producing cellulose makes it prospective as a biomass energy source and livestock feeding. Further, it can be transformed into high-cellulose content particles for applications in bioplastics, brake pads, and adsorbents. The current reports regarding education of water hyacinth to student also were added. Finally, issues and suggestions for future development related to the use of water hyacinths are discussed. This study is expected to provide comprehensive knowledge on how to turn invasive water hyacinth plants into valuable products.

Lauric acid improves hormonal profiles, antioxidant properties, sperm quality and histomorphometric changes in testis and epididymis of streptozotocin-induced diabetic infertility rats - Nursarah Syamimi Anuar; Syahirah Ain Shafie; Muhammad Aiman Faris Maznan; Noor Syaffinaz Noor Mohamad Zin; Nur Ain Sabrina Azmi; Rohaizad Abdul Raoof; Diyas Myrzakozha; Nurdiana Samsulrizal (Toxicology and Applied Pharmacology, 2023)

The presence of polycyclic aromatic hydrocarbons (PAHs) in air particles and estimation of the respiratory deposition flux - Nur Ain Nazirah Binti Najurudeen; Md Firoz Khan; Hamidah Suradi; Ummay Ayesha Mim; Israt Nur Janntul Raim; Sara Binte Rashid; Mohd Talib Latif; Muhammad Nurul Huda (Science of The Total Environment, 2023)

A crucial review on the challenges and recent gas membrane development for biogas upgrading - Nur Fajrina; Norhaniza Yusof; Ahmad Fauzi Ismail; Farhana Aziz; Muhammad Roil Bilad; Meshel Alkahtani (Journal of Environmental Chemical Engineering, 2023)

MoS2-TiO2 coated PVDF-based hollow fiber membranes for permeate flux enhancement in membrane distillation - Nurul Syazana Fuzil; Nur Hidayati Othman; Nur Hashimah Alias; Fauziah Marpani; Muhammad Shafiq Mat Shayuti; Munawar Zaman Shahruddin; Mohd Rizuan Mohd Razlan; Norazah Abd Rahman; Woei Jye Lau; Mohd Hafiz Dzarfan Othman; Ahmad Fauzi Ismail; Tutuk Djoko Kusworo; et al. (Journal of Environmental Chemical Engineering, 2023)

Current Status of Coral Reef Fish Abundances at Pulau Bidong and Nearby Islands, South China Sea Using Stereo-Diver Operated Video System - Aminudin Muhammad Afiq-Firdaus; Che Din Mohd Safuan; Suhaidi Shafie; Lila Iznita Izhar; Ezmahamrul Afreen Awalludin; Muhammad Faiz Ahmad; Nur Arbaeen Mohd Johari; Zainudin Bachok (Ocean Science Journal, 2023)

Synthesis of vinyl trimethyl silane and acrylic acid modified silica nanoparticles as corrosion inhibition protocols in saline medium - Tawfik A. Saleh; Mauliady Satria; Mulya Muhammad Nur; Norah Aljeaban; Bader Alharbi (Fuel, 2023)

Potential of agroforestry orchards as a conservation set-aside initiative in industrial rubber tree and oil palm plantations for avian biodiversity - Muhammad Syafiq Yahya; Sharifah Nur Atikah; Izereen Mukri; Aslinda Oon; Ainil Hawa; Ruzana Sanusi; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (Biodiversity and Conservation, 2023)

Spatial prediction of soil erosion risk using knowledge-driven method in Malaysia’s Steepland Agriculture Forested Valley - Nur Syabeera Begum Nasir Ahmad; Firuza Begham Mustafa; Safiah Yusmah Muhammad Yusoff (Environment, Development and Sustainability, 2023)

Graphene loaded TiO2 submicron spheres scattering layer for efficient dye-sensitized solar cell - Muhammad Umair Shahid; Norani Muti Mohamed; Ali Samer Muhsan; Siti Nur Azella Zaine; Mehboob Khatani; Asfand Yar; Waqar Ahmad; Muhammad Babar Hussain; Asma A. Alothman; Mohammed Sheikh Saleh Mushab (Chemosphere, 2023)

Mangrove species mapping through phenological analysis using random forest algorithm on Google Earth Engine - Muhammad Ari Purnomo Aji; Muhammad Kamal; Nur Mohammad Farda (Remote Sensing Applications: Society and Environment, 2023)

The effect of different in-line mixers producing emulsifier-free bio-diesel emulsion on the diesel engine combustion performance and exhaust emission - Wan Nur Izzati Wan Mahdi; Ahmad Muhsin Ithnin; Wira Jazair Yahya; Muhammad Adib Abdul Rashid; Hasannuddin Abd Kadir; Dhani Avianto Sugeng; Kinoshita Eiji (Fuel, 2023)

Understanding the quality and potential of groundwater for human purposes and peat fire disaster mitigation - Nur Islami; Mitri Irianti; Azhar Azhar; Muhammad Nor; Fakhruddin Fakhruddin (Arabian Journal of Geosciences, 2023)

Morphometric and genetic variations of four dominant species of snappers (Lutjanidae) harvested from the Northern Coast of Aceh waters, Indonesia - Sri Riska Rahayu; Zainal A. Muchlisin; Nur Fadli; Nanda Muhammad Razi; Mutia Ramadhaniaty; Luvi Syafrida Handayani; Siti Maulida; Firman M. Nur; Nurlaili Nurlaili; Moh N. Siti-Azizah (Zoologischer Anzeiger, 2023)

Does human movement-induced airflow elevate infection risk in burn patient’s isolation ward? A validated dynamics numerical simulation approach - Huiyi Tan; Keng Yinn Wong; Mohd Hafiz Dzarfan Othman; Bemgba Bevan Nyakuma; Desmond Daniel Chin Vui Sheng; Hong Yee Kek; Wai Shin Ho; Haslenda Hashim; Meng Choung Chiong; Muhammad Afiq Zubir; Nur Haliza Abdul Wahab; Syie Luing Wong; et al. (Energy and Buildings, 2023)

Green surface functionalization of chitosan with spent tea waste extract for the development of an efficient adsorbent for aspirin removal - Abu Hassan Nordin; Norzita Ngadi; Rushdan Ahmad Ilyas; Nur Aien Fatini Abd Latif; Muhammad Luqman Nordin; Mohd Syahlan Mohd Syukri; Walid Nabgan; Syafikah Huda Paiman (Environmental Science and Pollution Research, 2023)

Numerical investigation of fully confined RC column with carbon fiber reinforced polymer when expose to fire - Nur Aqilah Zakaria; Ruqayyah Ismail; Fariz Aswan Ahmad Zakwan; Hazrina Ahmad; Muhamad Firdaus Rosle; Mohd Hisbany Mohd Hashim; Raizal Saifulnaz Muhammad Rashid (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

The potential of shear wave velocity as an erosion risk index - Norinah Abd Rahman; Muhammad Ali Rehman; Nur Afiqah Zahari; Aizat Mohd Taib; Wan Hanna Melini Wan Mohtar; Ahmad Bukhari Ramli; Aniza Ibrahim; Dayang Zulaika Abang Hasbollah; Sadia Mannan Mitu; Mohamad Faizal Nurddin (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Characterisation and selection of freshwater cyanobacteria for phycobiliprotein contents - Hui Teng Tan; Fatimah Md. Yusoff; Yam Sim Khaw; Muhammad Farhan Nazarudin; Nur Amirah Izyan Noor Mazli; Siti Aqlima Ahmad; Noor Azmi Shaharuddin; Tatsuki Toda (Aquaculture International, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Construction of microbial electrodialysis cells equipped with internal proton migration pathways: Enhancement of wastewater treatment, desalination, and hydrogen production - Mohd Nur Ikhmal Salehmin; Muhammad Farhan Hil Me; Wan Ramli Wan Daud; Nazlina Haiza Mohd Yasin; Mimi Hani Abu Bakar; Abu Bakar Sulong; Swee Su Lim (Science of The Total Environment, 2023)

Transport viable heart tissue at physiological temperature yielded higher human cardiomyocytes compared to the conventional temperature - Muhammad Arza Putra; Normalina Sandora; Suwarti; Retno Wahyu Nurhayati; Raisa Nauli; Tyas Rahmah Kusuma; Nur Amalina Fitria; Ardiansyah; Chaidar Muttaqin; William Makdinata; Idrus Alwi (Cell and Tissue Banking, 2022)

Seed morphological traits associated with weedy rice escaped from imazapic+imazapyr herbicide treatment - Amalia Qistina Zulrushdi; Nur Ardiyana Rejab; Intan Filzah Mahmod; Zulqarnain Mohamed; Muhammad Nazri Ishak; Muhamad Shakirin Mispan (Phytoparasitica, 2022)

Quantification of Rock Mass Condition Based on Fracture Frequency Using Unmanned Aerial Vehicle Survey for Slope Stability Assessment - Muhammad Junaid; Rini Asnida Abdullah; Radzuan Sa’ari; Hafeezur Rehman; Kausar Sultan Shah; Rafi Ullah; Mohd Nur Asmawisham Alel; Ir. Zuraini Zainal; Nurul Eilmy Zainuddin (Journal of the Indian Society of Remote Sensing, 2022)

Carbon Stock Profiling of Mangrove Ecosystem in the Semarang-Demak Coastal Area for Global Warming Mitigation - Andin Irsadi; Nugroho Edi Kartijono; Partaya Partaya; Muhammad Abdullah; Lutfia Nur Hadiyanti; Halim Sukma Aji (International Journal of Environmental Research, 2022)

Characterisation of the single-cell human cardiomyocytes taken from the excess heart tissue of the right ventricular outlet in congenital heart disease - Normalina Sandora; Muhammad Arza Putra; Retno Wahyu Nurhayati; Suwarti; Raisa Nauli; Tyas Rahmah Kusuma; Nur Amalina Fitria; Ardiansyah; Chaidar Muttaqin; William Makdinata; Idrus Alwi (Cell and Tissue Banking, 2022)

Correction to: Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2022)

Assessment of Malaysian brown seaweed Padina gymnospora antioxidant properties and antimicrobial activity in different solvent extractions - Muhammad Farhan Nazarudin; Muhammad Syazwan Shahidan; Nur Amirah Izyan Noor Mazli; Tan Hui Teng; Yam Sim Khaw; Ina Salwany Md Yasin; Azizul Isha; Mohammed Aliyu-Paiko (Fisheries Science, 2022)

Mass Transfer Kinetics and Mechanisms of Phosphate Adsorbed on Waste Mussel Shell - Nur Atikah Abdul Salim; Mohamad Ali Fulazzaky; Mohd Hafiz Puteh; Mohd Hairul Khamidun; Abdull Rahim Mohd Yusoff; Noorul Hudai Abdullah; Mohammad Fulazzaky; Muhammad Abbas Ahmad Zaini (Water, Air, & Soil Pollution, 2022)

Reliability of the Mass Transfer Factor Models to Describe the Adsorption of NH4+ by Granular Activated Carbon - Mohamad Ali Fulazzaky; Nur Atikah Abdul Salim; Mohd Hafiz Puteh; Mohd Hairul Khamidun; Abdull Rahim Mohd Yusoff; Mohammad Fulazzaky; Noorul Hudai Abdullah; Muhammad Abbas Ahmad Zaini (International Journal of Environmental Research, 2022)

Biogas Production Through Mono- and Co-digestion of Pineapple Waste and Cow Dung at Different Substrate Ratios - Adila Fazliyana Aili Hamzah; Muhammad Hazwan Hamzah; Hasfalina Che Man; Nur Syakina Jamali; Shamsul Izhar Siajam; Pau Loke Show (BioEnergy Research, 2022)

Characterisation of graphene oxide-coated sand for potential use as proppant in hydraulic fracturing - Ainni Syuhada Ramlan; Rohani Mohd Zin; Noor Fitrah Abu Bakar; Nur Hidayati Othman; Husna Hayati Jarni; Mohamed Hasaan Hussain; Nabil Imran Mohd Najib; Muhammad Zulhasbullah Zakran (Arabian Journal of Geosciences, 2022)

Assessment of contaminants in sand production from petroleum wells offshore Sabah - Muhammad Shafiq Mat Shayuti; Suzalina Zainal; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Munawar Zaman Shahruddin; Nur Hidayati Othman; Nur Hashimah Alias; Tengku Amran Tengku Mohd; Rahida Wati Sharudin (Environmental Science and Pollution Research, 2022)

Surveillance of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) in high-rise apartment buildings in Selangor, Malaysia - Muhammad Aidil Roslan; Romano Ngui; Indra Vythilingam; Kien Fatt Chan; Poo Soon Ong; Ching Keat Low; Nur Hidayah Muhammed; Wan Yusoff Wan Sulaiman (International Journal of Tropical Insect Science, 2022)

Preparation of Cell-Seeded Heart Patch In Vitro; Co-Culture of Adipose-Derived Mesenchymal Stem Cell and Cardiomyocytes in Amnion Bilayer Patch - Normalina Sandora; Muhammad Arza Putra; Pribadi Wiranda Busro; Ardiansyah; Chaidar Muttaqin; William Makdinata; Nur Amalina Fitria; Tyas Rahmah Kusuma (Cardiovascular Engineering and Technology, 2022)

Can heat shock protein 70 (HSP70) serve as biomarkers in Antarctica for future ocean acidification, warming and salinity stress? - Nur Athirah Yusof; Makdi Masnoddin; Jennifer Charles; Ying Qing Thien; Farhan Nazaie Nasib; Clemente Michael Vui Ling Wong; Abdul Munir Abdul Murad; Nor Muhammad Mahadi; Izwan Bharudin (Polar Biology, 2022)
The Antarctic Peninsula is one of the fastest-warming places on Earth. Elevated sea water temperatures cause glacier and sea ice melting. When icebergs melt into the ocean, it “freshens” the saltwater around them, reducing its salinity. The oceans absorb excess anthropogenic carbon dioxide (CO 2 ) causing decline in ocean pH, a process known as ocean acidification. Many marine organisms are specifically affected by ocean warming, freshening and acidification. Due to the sensitivity of Antarctica to global warming, using biomarkers is the best way for scientists to predict more accurately future climate change and provide useful information or ecological risk assessments. The 70-kilodalton (kDa) heat shock protein (HSP70) chaperones have been used as biomarkers of stress in temperate and tropical environments. The induction of the HSP70 genes ( Hsp70 ) that alter intracellular proteins in living organisms is a signal triggered by environmental temperature changes. Induction of Hsp70 has been observed both in eukaryotes and in prokaryotes as response to environmental stressors including increased and decreased temperature, salinity, pH and the combined effects of changes in temperature, acidification and salinity stress. Generally, HSP70s play critical roles in numerous complex processes of metabolism; their synthesis can usually be increased or decreased during stressful conditions. However, there is a question as to whether HSP70s may serve as excellent biomarkers in the Antarctic considering the long residence time of Antarctic organisms in a cold polar environment which appears to have greatly modified the response of heat responding transcriptional systems. This review provides insight into the vital roles of HSP70 that make them ideal candidates as biomarkers for identifying resistance and resilience in response to abiotic stressors associated with climate change, which are the effects of ocean warming, freshening and acidification in Antarctic organisms.

Effects of dietary palm oil on broiler chicken productive performance and carcass characteristics: a comprehensive review - Mookiah Saminathan; Wan Nooraida Wan Mohamed; ‘Abidah Md Noh; Nur Atikah Ibrahim; Muhammad Amirul Fuat; Suriya Kumari Ramiah (Tropical Animal Health and Production, 2022)

Removal of emerging contaminants by emulsion liquid membrane: perspective and challenges - Nur Dina Zaulkiflee; Abdul Latif Ahmad; Nuur Fahanis Che Lah; Meor Muhammad Hafiz Shah Buddin (Environmental Science and Pollution Research, 2022)

Correction to: The effect of salinity on the interaction between microplastic polyethylene terephthalate (PET) and microalgae Spirulina sp. - Hadiyanto Hadiyanto; Muslihuddin Muslihuddin; Adian Khoironi; Wahyu Zuli Pratiwi; Muthia’ah Nur Fadlilah; Fuad Muhammad; Norma Afiati; Inggar Dianratri (Environmental Science and Pollution Research, 2022)

The effect of salinity on the interaction between microplastic polyethylene terephthalate (PET) and microalgae Spirulina sp. - Hadiyanto Hadiyanto; Muslihuddin Muslihuddin; Adian Khoironi; Wahyu Zuli Pratiwi; Muthia’ah Nur Fadlilah; Fuad Muhammad; Norma Afiati; Inggar Dianratri (Environmental Science and Pollution Research, 2022)

Two new 2-arylbenzofurans from Sesbania grandiflora L. and their cytotoxicity towards cancer cell - Tjitjik Srie Tjahjandarie; Mulyadi Tanjung; Ratih Dewi Saputri; Devina Oktari Rahayu; Alfiah Nur Irza Gunawan; Muhammad Fajar Aldin (Natural Product Research, 2021)

Exploring the effect of ultrasonic power, frequency, and load toward remediation of oil-contaminated beach and oilfield sands using ANOVA - Muhammad Shafiq Mat-Shayuti; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Nur Hidayati Othman; Nur Hashimah Alias (Environmental Science and Pollution Research, 2021)

Effects of vegetable oil supplementation on rumen fermentation and microbial population in ruminant: a review - Nur Atikah Ibrahim; Abdul Razak Alimon; Halimatun Yaakub; Anjas Asmara Samsudin; Su Chui Len Candyrine; Wan Nooraida Wan Mohamed; Abidah Md Noh; Muhammad Amirul Fuat; Saminathan Mookiah (Tropical Animal Health and Production, 2021)

Biomechanical analysis of three different types of fixators for anterior cruciate ligament reconstruction via finite element method: a patient-specific study - Nur Afikah Zainal Abidin; Abdul Hadi Abdul Wahab; Rabiatul Adibah Abdul Rahim; Mohammed Rafiq Abdul Kadir; Muhammad Hanif Ramlee (Medical & Biological Engineering & Computing, 2021)

Recent Advances on Coagulation-Based Treatment of Wastewater: Transition from Chemical to Natural Coagulant - Muhammad Burhanuddin Bahrodin; Nur Syamimi Zaidi; Norelyza Hussein; Mika Sillanpää; Dedy Dwi Prasetyo; Achmad Syafiuddin (Current Pollution Reports, 2021)

Effect of compaction on soil CO2 and CH4 fluxes from tropical peatland in Sarawak, Malaysia - Nur Azima Busman; Nagamitsu Maie; Che Fauziah Ishak; Muhammad Firdaus Sulaiman; Lulie Melling (Environment, Development and Sustainability, 2021)

Isolation and characterization of bacteria from fermented cooked-rice - Md. Sojiur Rahman; Md. Sohel Rana; Md. Biplob Hosen; Md. Ahsan Habib; Asaduzzaman Nur; Mst. Kusum Kaly; Muhammad Nurul Matin; Khondokar Nasirujjaman; Md Motiur Rahman (Biologia, 2021)

Candidate Rlm6 resistance genes against Leptosphaeria. maculans identified through a genome-wide association study in Brassica juncea (L.) Czern - Hua Yang; Nur Shuhadah Mohd Saad; Muhammad Ishaq Ibrahim; Philipp E. Bayer; Ting Xiang Neik; Anita A. Severn-Ellis; Aneeta Pradhan; Soodeh Tirnaz; David Edwards; Jacqueline Batley (Theoretical and Applied Genetics, 2021)

Abundance and species composition of synchronous flashing firefly at Sungai Rembau, Negeri Sembilan, Malaysia - Lailatul-Nadhirah Asri; Nur-Athirah Abdullah; Azman Sulaiman; Muhammad Hazwan Mohd Asri; Norela Sulaiman; Engku Muhamad Faris Engku Nasrullah Satiman; Shahril Mod Husin; Aisah Md Shukor; Nurul Darsani Amat Darbis (International Journal of Tropical Insect Science, 2021)

A preliminary studies to assess public knowledge of beach safety in east coast Malaysia - Nur Adawiyah Mohammed Isa; Muhammad Zahir Ramli; Siti Fairuz Che Othman; Muhammad Zubir Yusof (Natural Hazards, 2021)

Sustainability of Palm Biodiesel in Transportation: a Review on Biofuel Standard, Policy and International Collaboration Between Malaysia and Colombia - Mohd Nur Ashraf Mohd Yusoff; Nurin Wahidah Mohd Zulkifli; Nazatul Liana Sukiman; Ong Hwai Chyuan; Masjuki Haji Hassan; Muhammad Harith Hasnul; Muhammad Syahir Amzar Zulkifli; Muhammad Mujtaba Abbas; Muhammad Zulfattah Zakaria (BioEnergy Research, 2021)

Photocatalytic performance improvement by utilizing GO_MWCNTs hybrid solution on sand/ZnO/TiO2-based photocatalysts to degrade methylene blue dye - Nur Jannah Idris; Suriani Abu Bakar; Azmi Mohamed; Muqoyyanah Muqoyyanah; Mohd Hafiz Dzarfan Othman; Mohamad Hafiz Mamat; Mohd Khairul Ahmad; Muhammad Danang Birowosuto; Tetsuo Soga (Environmental Science and Pollution Research, 2021)

Potential Risk and Occupational Exposure of Pesticides Among Rice Farmers of a Village Located in Northern Peninsular of Malaysia - Nur Anis Ahmad; Ali Salehabadi; Syahidah Akmal Muhammad; Mardiana Idayu Ahmad (Exposure and Health, 2020)

Effect of Water Temperature on Survival, Growth and Molting Cycle During Early Crablet Instar of Mud Crab, Scylla paramamosain (Estampador, 1950) - Muhammad Nur Syafaat; Syahnon Mohammad; Mohamad Nor Azra; Hongyu Ma; Ambok Bolong Abol-Munafi; Mhd Ikhwanuddin (Thalassas: An International Journal of Marine Sciences, 2020)

Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2020)

Application of geoelectrical resistivity method for the assessment of shallow aquifer quality in landfill areas - Nur Islami; Mitri Irianti; Fakhruddin Fakhruddin; Azhar Azhar; Muhammad Nor (Environmental Monitoring and Assessment, 2020)

Evaluation of edible bird’s nest processing plant wastewater quality: a factory case study - Siti Shahara Zulfakar; Farah Natasha Haezam; Mohd Sham Othman; Nur Faizah Abu Bakar; Muhammad Ikram A. Wahab (Arabian Journal of Geosciences, 2020)

Evaluation of Diffusivity and Wettability of Crude Oil-Contaminated Sand from Offshore Petroleum Facility Prior to Remediation Process - Muhammad Shafiq Mat-Shayuti; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Nur Hashimah Alias; Nur Hidayati Othman; Suzalina Zainal (Water, Air, & Soil Pollution, 2020)

Analysis of the application of an advanced classifier algorithm to ultra-high resolution unmanned aerial aircraft imagery – a neural network approach - Fatwa Ramdani; Muhammad Tanzil Furqon; Budi Darma Setiawan; Alfi Nur Rusydi (International Journal of Remote Sensing, 2020)

Detection of porcine pepsin in model cheese using polyclonal antibody-based ELISA - Raja Mohd Hafidz Raja Nhari; Azyan Nafisah Muhammad Zailani; Nur Fadhilah Khairil Mokhtar; Irwan Hanish (Food Additives & Contaminants: Part A, 2020)

Mineral carbonation of sedimentary mine waste for carbon sequestration and potential reutilization as cementitious material - Faradiella Mohd Kusin; Sharifah Nur Munirah Syed Hasan; Muhammad Afiq Hassim; Verma Loretta M. Molahid (Environmental Science and Pollution Research, 2020)

Diverse and dynamic roles of F-box proteins in plant biology - Nur-Athirah Abd-Hamid; Muhammad-Izzat Ahmad-Fauzi; Zamri Zainal; Ismanizan Ismail (Planta, 2020)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)

Overview performance of lanthanide oxide catalysts in methanation reaction for natural gas production - Salmiah Jamal Mat Rosid; Susilawati Toemen; Malik Muhammad Asif Iqbal; Wan Azelee Wan Abu Bakar; Wan Nur Aini Wan Mokhtar; Md Maniruzzaman A. Aziz (Environmental Science and Pollution Research, 2019)

Progress in ultrasonic oil-contaminated sand cleaning: a fundamental review - Muhammad Shafiq Mat-Shayuti; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Putri Nadzrul Faizura Megat Khamaruddin; Nur Hidayati Othman (Environmental Science and Pollution Research, 2019)

An outbreak of leptospirosis among reserve military recruits, Hulu Perdik, Malaysia - Vasantha Kumari Neela; Nurul Natasya Azhari; Narcisse Joseph; Noraini Philip Mimie; Siti Nur Alia Ramli; Nooreen Farzana Mustapha; Siti Nabilah Ishak; Farah Shafawati Mohd-Taib; Muhammad Afif Yusof; Mohd Nasir Mohd Desa; Garba Bashiru; Zamberi Sekawi (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Diesel engine emission analysis using fuel from diverse emulsification methods - Dhani Avianto Sugeng; Wira Jazair Yahya; Ahmad Muhsin Ithnin; Muhammad Adib Abdul Rashid; Nur Salsabilla Mohd Syahril Amri; Hasannuddin Abd Kadir; Mohd Naim Abdul Halim (Environmental Science and Pollution Research, 2018)

Trends and variations in the prescribing of secondary preventative cardiovascular therapies for non-ST elevation myocardial infarction (NSTEMI) in Malaysia - Padmaa Venkatason; Nur Lisa Zaharan; Muhammad Dzafir Ismail; Wan Azman Wan Ahmad; Ahmad Syadi Mahmood Zuhdi (European Journal of Clinical Pharmacology, 2018)

Monoclonal antibody-based enzyme immunoassay for detection of porcine plasma in fish surimi - Raja Mohd Hafidz Raja Nhari; Nur Fadhilah Khairil Mokhtar; Irwan Hanish; Muhajir Hamid; Muhammad Asraf Alif Mohamed Rashidi; Nur Maisarah Shahidan (Food Additives & Contaminants: Part A, 2018)

Spatio-Temporal Patterns in Coral Reef Communities of the Spermonde Archipelago, 2012–2014, I: Comprehensive Reef Monitoring of Water and Benthic Indicators Reflect Changes in Reef Health - Mirta Teichberg; Christian Wild; Vanessa N. Bednarz; Hauke F. Kegler; Muhammad Lukman; Astrid A. Gärdes; Jasmin P. Heiden; Laura Weiand; Nur Abu; Andriani Nasir; Sara Miñarro; Sebastian C. A. Ferse; et al. (Frontiers in Marine Science, 2018)

Artificial Neural Network (ANN) for Modelling Adsorption of Lead (Pb (II)) from Aqueous Solution - Taimur Khan; Muhammad Raza Ul Mustafa; Mohamed Hasnain Isa; Teh Sabariah Binti Abd Manan; Yeek-Chia Ho; Jun-Wei Lim; Nur Zulaikha Yusof (Water, Air, & Soil Pollution, 2017)

Robust approach for optimal positioning and ranking potential rainwater harvesting structure (RWH): a case study of Iraq - Khamis Naba Sayl; Nur Shazwani Muhammad; Ahmed El-Shafie (Arabian Journal of Geosciences, 2017)

Estimation the Physical Variables of Rainwater Harvesting System Using Integrated GIS-Based Remote Sensing Approach - Khamis Naba Sayl; Nur Shazwani Muhammad; Zaher Mundher Yaseen; Ahmed El-shafie (Water Resources Management, 2016)

The use of FAMACHA in estimation of gastrointestinal nematodes and total worm burden in Damara and Barbados Blackbelly cross sheep - Konto Mohammed; Yusuf Abba; Nur Syairah Binti Ramli; Murugaiyah Marimuthu; Mohammed Ariff Omar; Faez Firdaus Jesse Abdullah; Muhammad Abubakar Sadiq; Abdulnasir Tijjani; Eric Lim Teik Chung; Mohammed Azmi Mohammed Lila (Tropical Animal Health and Production, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Experimental analysis of the effects of consumer exclusion on recruitment and succession of a coral reef system along a water quality gradient in the Spermonde Archipelago, Indonesia - Jeremiah G. Plass-Johnson; Jasmin P. Heiden; Nur Abu; Muhammad Lukman; Mirta Teichberg (Coral Reefs, 2016)

Development of MY-DRG casemix pharmacy service weights in UKM Medical Centre in Malaysia - Saad Ahmed Ali Jadoo; Syed Mohamed Aljunid; Amrizal Muhammad Nur; Zafar Ahmed; Dexter Van Dort (DARU Journal of Pharmaceutical Sciences, 2015)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Antinociceptive, anti-inflammatory, and antipyretic properties of an aqueous extract of Dicranopteris linearis leaves in experimental animal models - Zainul Amiruddin Zakaria; Zuleen Delina Fasya Abdul Ghani; Raden Nur Suraya Raden Mohd. Nor; Hanan Kumar Gopalan; Mohd. Roslan Sulaiman; Abdul Manan Mat Jais; Muhammad Nazrul Somchit; Arifah Abdul Kader; Johari Ripin (Journal of Natural Medicines, 2008)

Cloning of Lactobacillus plantarum IAM 12477 lysine biosynthetic genes encoding functional aspartate semialdehyde dehydrogenase, dihydrodipicolinate synthase, and dihydrodipicolinate reductase - Muhammad Nur Cahyanto; Hiroko Kawasaki; Kazuhito Fujiyama; Tatsuji Seki (World Journal of Microbiology and Biotechnology, 2006)